Polyethylene composition and biaxially stretched film comprising same

By adjusting the lace-up molecular fraction and crystal structure of the ethylene-α-olefin copolymer and combining with the metallocene catalyst, the problem of insufficient stability and shrinkage resistance of polyethylene resin during the stretching process is solved, and high shrinkage resistance and A biaxial stretch film with mechanical properties is suitable for packaging and reduces the difficulty of material recycling.

CN119183466APending Publication Date: 2024-12-24LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040097.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-02
Filing Date
2023-09-07
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing polyethylene resin lacks sufficient tensile stability and shrinkage resistance during the stretching process, making it difficult to apply to biaxial stretching process, and commercially available packaging film materials cannot be recycled, resulting in an increase in demand for a single material.

Method used

A polyethylene composition containing ethylene-α-olefin copolymer was developed to improve the natural stretch ratio and elongation of break by adjusting the lace-up molecular fraction and crystal structure, combining metallocene catalysts to optimize mechanical properties and productivity.

Benefits of technology

A biaxial stretch film with high shrinkage resistance, tensile stability and excellent mechanical properties is achieved, which is suitable for packaging and has good recycling potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119183466A_ABST
    Figure CN119183466A_ABST
Patent Text Reader

Abstract

The present invention relates to a polyethylene composition which maintains excellent mechanical properties and is suitable for a biaxially stretched film due to excellent tensile stability and high shrinkage resistance, and a biaxially stretched film comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0120055 filed on September 22, 2022, and Korean Patent Application No. 10-2022-0144767 filed on November 2, 2022, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference. Technical Field

[0003] The present invention relates to a polyethylene composition suitable for a biaxially stretched film having excellent tensile stability and high shrinkage resistance while maintaining excellent mechanical properties, and a biaxially stretched film comprising the polyethylene composition. Background Art

[0004] Film products made of linear low-density polyethylene (LLDPE) and / or high-density polyethylene (HDPE) are widely used in packaging such as commodity bags, grocery bags, food packaging and specialty packaging, and industrial liners. In these applications, shrink films that can wrap products while maintaining their shape are mainly used to protect products from being touched during display.

[0005] In particular, among these shrink films, biaxially stretched polymer films are widely used in the field of packaging due to their excellent mechanical properties, productivity and printability. Commercially available packaging films generally use BOPP (biaxially stretched polypropylene), BOPET (biaxially stretched polyethylene terephthalate) or BOPA (biaxially stretched polyamide) as the printing layer and LLDPE as the sealing layer. These composite materials cannot be recycled, and due to regulations on the recycling of packaging materials, the demand for single materials is increasing. Therefore, research and development is currently underway to manufacture single-material packaging films using biaxially stretched polyethylene (BOPE) films instead of printing layer films.

[0006] However, commercially available polyethylene (PE) resins do not have sufficient tensile stability and may break and melt during stretching, making them difficult to apply to biaxial stretching processes. In order to ensure tensile stability, products in the form of polyethylene compositions containing resins with low density and high melt index have been developed. However, due to the low rigidity, shrinkage and impact resistance of the above compositions, they are not suitable as PE resins for biaxially stretched films.

[0007] Therefore, a method of selecting a PE resin having a molecular structure conducive to stretching and selecting an appropriate composition is required so that a PE composition for biaxial stretching that exhibits stretching stability during biaxial stretching and has good film mechanical properties can be provided. Summary of the invention

[0008] [Technical issues]

[0009] The present invention relates to a polyethylene composition capable of preparing a biaxially stretched film having high shrinkage resistance, tensile stability and transparency while maintaining excellent mechanical properties, and a biaxially stretched film comprising the polyethylene composition.

[0010] [Technical solution]

[0011] In one embodiment of the present invention, there is provided a polyethylene composition comprising at least one ethylene-α-olefin copolymer,

[0012] The tethered molecule fraction obtained from the crystallinity and crystal structure analysis results is 4.5 wt % to 7.0 wt %, and

[0013] The natural draw ratio (NDR) measured by tensile measurement at a tensile speed of 500% / min on a sheet specimen having a thickness of 1 mm according to ASTM D638 is 600% or more.

[0014] In another embodiment of the present invention, a biaxially stretched film comprising the polyethylene composition of the above embodiment is provided.

[0015] Hereinafter, a polyethylene composition and a biaxially stretched film according to embodiments of the present invention will be described in detail.

[0016] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0017] Unless the context clearly indicates otherwise, singular forms also include plural forms.

[0018] In the present invention, the terms “comprises”, “includes” or “has” are used to describe the features, numbers, steps, components or a combination thereof, but do not exclude the addition of one or more other features, numbers, steps, components or a combination thereof.

[0019] The term "about" or "substantially" is intended to have the meaning of an approximate numerical value or range allowing for an error, and is intended to prevent the exact or absolute numerical value disclosed for understanding the present invention from being illegally or unfairly used by any unscrupulous third party.

[0020] Furthermore, in the present invention, the (co)polymer also includes a homopolymer and a copolymer.

[0021] Unless otherwise defined herein, “copolymerization” may refer to block copolymerization, random copolymerization, graft copolymerization or alternating copolymerization, and “copolymer” may refer to block copolymer, random copolymer, graft copolymer or alternating copolymer.

[0022] Since the present invention can be variously modified and has various forms, its specific embodiments will be described in detail by example. However, this does not mean that the present invention is limited to the specific form disclosed, and it should be understood that the present invention includes all modifications, equivalents and substitutions within the concept and technical scope of the present invention.

[0023] Polyethylene composition

[0024] In one embodiment of the present invention, there is provided a polyethylene composition comprising at least one ethylene-α-olefin copolymer,

[0025] wherein the tethered molecule fraction obtained from the crystallinity and crystal structure analysis results is 4.5 wt % to 7.0 wt %, and

[0026] According to ASTM D638, the natural draw ratio (NDR) measured by tensile test at a tensile speed of 500% / min on a sheet specimen having a thickness of 1 mm is 600% or more.

[0027] For reference, "parts by weight" used herein refers to a relative concept of the ratio of the weight of the remaining materials to the weight of a specific material. For example, in a mixture containing 50 g of material A, 20 g of material B, and 30 g of material C, based on 100 parts by weight of material A, the amounts of material B and C are 40 parts by weight and 60 parts by weight, respectively.

[0028] Meanwhile, "wt% (weight %)" refers to an absolute concept expressing the weight of a specific material as a percentage based on the total weight. In the above mixture, based on 100% of the total weight of the mixture, the contents of materials A, B and C are 50 weight %, 20 weight % and 30 weight %, respectively.

[0029] In the polyethylene composition of one embodiment, a first ethylene-α-olefin copolymer having excellent fluidity to impart stretchability by using a specific metallocene catalyst (to be described separately below) is mixed with a second ethylene-α-olefin copolymer having excellent mechanical properties, so that the balance between mechanical properties and elongation can be adjusted. Therefore, it has the characteristics of being suitable for manufacturing a biaxially stretched film having high shrinkage resistance, printability and transparency while maintaining mechanical properties, productivity and stretching stability that are the same as or better than those of conventional films.

[0030] The polyethylene composition may include, for example: (a) a polyethylene having a density of 0.930 g / cm 3 Up to 0.960g / cm 3 And melt index (MI 2.16, 190 ° C, 2.16 kg load) of 0.2 g / 10min to 2.0 g / 10min of the first ethylene - α-olefin copolymer; and (b) a density of 0.870 g / cm 3 Up to 0.920g / cm 3 And melt index (MI 2.16 , 190° C., 2.16 kg load) in a range of 3.0 g / 10 min to 10.0 g / 10 min of a second ethylene-α-olefin copolymer, wherein each copolymer is produced by using a metallocene catalyst.

[0031] In particular, the polyethylene composition of one embodiment may have ideal crystal characteristics, crystal structure and tie molecule fraction due to the first ethylene-α-olefin copolymer and the second ethylene-α-olefin copolymer of the predetermined composition. More specifically, the polyethylene composition of one embodiment may show partial crystallinity, including amorphous regions between crystalline regions and crystalline regions containing a lamellar structure. Tie molecules may be included in the amorphous region to connect the thin sheets, and the tie molecule fraction may affect the elasticity of the polyethylene composition.

[0032] The polyethylene composition of one embodiment can exhibit excellent tensile properties and tensile stability by having an appropriate tie molecule fraction. In addition, the content of the crystalline region is also optimized, and can provide excellent mechanical properties and transparency when made into a biaxially stretched film.

[0033] In a more specific embodiment, according to the crystallinity and crystal structure analysis results, the polyethylene composition may have a tether molecule fraction of 4.5 wt % to 7.0 wt %, 4.9 wt % to 6.5 wt %, or 5.0 wt % to 6.0 wt %. When the tether molecule fraction is too small, the tensile strength and tensile stability of the composition may be reduced, making it difficult to manufacture a biaxially stretched film with excellent mechanical properties. When the tether molecule fraction is too high, the composition may be susceptible to strain hardening during the stretching process, making the stretching itself difficult.

[0034] The molecular weight, melting point and crystallinity (DSC) analysis results of the composition of the present embodiment can be used to calculate the molecular weight, melting point and crystallinity (DSC) of the composition according to the following equations 1 to 4. The method for calculating the molecular weight is also described in U.S. Pat. No. 10,775,287:

[0035] [Equation 1]

[0036]

[0037] In Equation 1, n is dw / dM (where M is the molecular weight of the ethylene (co)polymer), P can be calculated by the following Equation 2, dM is dlogM<x-axis data of the GPC curve, Xn+1> - dlogM<x-axis data of the GPC curve, Xn>.

[0038] [Equation 2]

[0039]

[0040] In Equation 2, r is the end-to-end distance of the random coil, b 2 is 3 / 2 <r> 2 , l c is the crystal thickness of the following equation 3;

[0041] [Equation 3]

[0042]

[0043] In equation 3, Tm is the melting temperature of the ethylene (co)polymer, T m 0 is 415K, σ e 60.9×10 -3 Jm- 2 , Δh m 2.88×10 3 Jm- 3 , l a is the amorphous layer thickness of Equation 4, <r>It can be calculated as 2×lc+la;

[0044] [Equation 4]

[0045] l a =ρ c l c (1-ω c ) / ρ a ω c

[0046] In Equation 4, ρ c is the density of the crystalline phase, which is 1000 kg / m 3 , ρ a is the density of the amorphous phase, which is 852 kg / m 3 ,ω c is the crystallinity weight fraction.

[0047] In addition, by adding the first ethylene-α-olefin copolymer and the second ethylene-α-olefin copolymer to the optimal composition, the natural stretch ratio (NDR) of the composition of one embodiment can be greater than 600%, from 600% to 1000%, or from 650% to 900%, wherein the natural stretch ratio is defined as: the elongation before the strain hardening point of the tensile curve when the composition is processed into a sheet specimen with a thickness of 1 mm and a tensile test is performed at a tensile rate of 500% / min at room temperature (about 25°C) according to the ASTM D638 standard.

[0048] In addition, the elongation at break of the composition in one embodiment may be greater than 3000%, from 3000% to 4500%, or from 3100% to 4000%, wherein the elongation at break is defined as the elongation at break of the sample when the composition is processed into a sheet sample with a thickness of 1 mm and a tensile test is performed at a tensile rate of 1000% / min at about 120° C. according to ASTM D638.

[0049] In addition, according to the ASTM D638 standard, a tensile test is performed at a tensile rate of 1000% / min at about 120°C. According to the high-temperature tensile test results, the yield strength of the composition of one embodiment at 120°C may be greater than 4.0 MPa, 4.0 MPa to 6.0 MPa, or 4.5 MPa to 5.0 MPa, and the 1% modulus may be greater than 4.0 MPa, 4.0 to 6.0 MPa, or 4.2 to 5.0 MPa.

[0050] These natural stretch ratios and elongation at break define that the composition of one embodiment has excellent elasticity, stretchability and stretch stability, and the composition of one embodiment satisfying these physical properties can produce a biaxially stretched film having excellent mechanical properties.

[0051] At the same time, the density of the polyethylene composition can be 0.925 g / cm 3 Above 0.939g / cm 3 Preferably, the density can be 0.927 g / cm 3 Above, 0.929g / cm 3 Above, or 0.931g / cm 3 Above, 0.938g / cm 3 Below, 0.937g / cm 3 Below, 0.936g / cm 3 Below, or 0.935g / cm 3 the following.

[0052] Density (g / cm 3 ) can be measured using a density gradient column according to ASTM D 1505 (American Society for Testing and Materials). For example, density (g / cm 3 ) is measured as described in Test Examples 1 and 2 below.

[0053] In addition, the melt index (MI) of the polyethylene composition 2.16 , 190°C, 2.16kg load) can be 0.3g / 10min to 1.5g / 10min. Preferably, the melt index (MI 2.16 , 190°C, 2.16kg load) can be more than 0.35g / 10min, more than 0.37g / 10min, or more than 0.4g / 10min, and less than 1.4g / 10min, less than 1.3g / 10min, less than 1.2g / 10min, or less than 1.1g / 10min.

[0054] Melt Index (MI 2.16 ) can be measured according to ASTM D 1238 (Condition E, 190°C, 2.16 kg) of the American Society for Testing and Materials at 190°C and a load of 2.16 kg. For example, the melt index (MI 2.16 ) is shown in Test Examples 1 and 2 described later.

[0055] In addition, the number average molecular weight (Mn) of the polyethylene composition can be 15000 g / mol or more, 17000 g / mol or more, or 19000 g / mol or more and 500000 g / mol or less, 300000 g / mol or less, 100000 g / mol or less, 50000 g / mol or less, or 31000 g / mol or less. The weight average molecular weight (Mw) of the polyethylene composition can be 100000 g / mol or more, or 106000 g / mol or more and 1000000 g / mol or less, 500000 g / mol or less, 300000 g / mol or less, or 158000 g / mol or less.

[0056] The molecular weight distribution (Mw / Mn) of the polyethylene composition may be 10.0 or less, or from 1.0 or more to 10.0 or less. More preferably, the molecular weight distribution (Mw / Mn) may be 9.5 or less, 9.0 or less, 8.5 or less, or 8.3 or less. In addition, the molecular weight distribution (Mw / Mn) may be 1.5 or more, 1.8 or more, 2.0 or more, 2.5 or more, 2.8 or more, 3.0 or more, or 3.4 or more.

[0057] In the present invention, weight average molecular weight (Mw) and number average molecular weight (Mn) are values ​​measured by GPC (gel permeation chromatography, manufactured by Water Company) and converted with standard polystyrene. However, weight average molecular weight is not limited thereto and can be measured by other methods known in the art. For example, the determination method of weight average molecular weight (Mw) and number average molecular weight (Mn) is as described in Test Examples 1 and 2 described later.

[0058] In addition, the polyethylene composition may have a melting point (Tm) of 127° C. to 130° C., a crystallization temperature (Tc) of 112° C. to 115° C., and a crystallinity (Xc) of 37% to 50%.

[0059] The melting point Tm, crystallization temperature Tc and crystallinity Xc can be measured using a differential scanning calorimeter (DSC, equipment name: DSC Q20, manufacturer: TA Instruments). For example, the method for measuring the melting point Tm, crystallization temperature Tc and crystallinity Xc is as described in Test Example 2 described later.

[0060] Meanwhile, the polyethylene composition of one embodiment of the present invention comprises a first ethylene-α-olefin copolymer (a) of more than 60% by weight and less than 90% by weight, and a second ethylene-α-olefin copolymer (b) of more than 10% by weight and less than 40% by weight. Preferably, the content of the first ethylene-α-olefin copolymer (b) can be more than 65% by weight, more than 67% by weight, or more than 70% by weight, and less than 85% by weight, less than 83% by weight, or less than 80% by weight. In addition, the content of the second ethylene-α-olefin copolymer (b) can be more than 15% by weight, more than 17% by weight, or more than 20% by weight, and less than 35% by weight, less than 33% by weight, or less than 30% by weight.

[0061] When the first ethylene-α-olefin copolymer and the second ethylene-α-olefin copolymer are combined in appropriate amounts, the composition of one embodiment may satisfy a suitable crystal structure and a tethered molecule fraction, and thus may satisfy all of the above-mentioned excellent physical properties.

[0062] In the polyethylene composition, the first ethylene-α-olefin copolymer and the second ethylene-α-olefin copolymer can each be a copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms. In a more specific embodiment, it can be a copolymer of ethylene and 1-butene, 1-hexene or 1-octene. In a specific embodiment, the first ethylene-α-olefin copolymer and the second ethylene-α-olefin copolymer can be the same or different from each other. For example, the first ethylene-α-olefin copolymer (a) can be an ethylene / 1-hexene copolymer, and the second ethylene-α-olefin copolymer (b) can be an ethylene / 1-octene copolymer.

[0063] First ethylene-α-olefin copolymer (a)

[0064] In the polyethylene composition of one embodiment of the present invention, the first ethylene-α-olefin copolymer (a) has excellent mechanical properties and is suitable for producing a biaxially stretched film having good stretchability and high mechanical properties and achieving an appropriate balance between crystallinity and processability.

[0065] Specifically, the density of the first ethylene-α-olefin copolymer (a) is 0.930 g / cm 3 Up to 0.960g / cm 3 Melt index (MI 2.16 , 190°C, 2.16kg load) is 0.2g / 10min to 2.0g / 10min.

[0066] Preferably, the density (a) of the first ethylene-α-olefin copolymer may be 0.933 g / cm 3 Above, 0.935g / cm 3 Above, 0.938g / cm 3 Above, or 0.941g / cm 3 Above, 0.955g / cm 3 Below, 0.950g / cm 3 Below, or 0.948g / cm 3 the following.

[0067] In addition, the melt index (MI) of the first ethylene-α-olefin copolymer (a) 2.16 , 190°C, 2.16 kg load) can be 0.2 g / 10 min or more and 1.5 g / 10 min or less, 1.0 g / 10 min or less, or 0.6 g / 10 min or less.

[0068] The first ethylene-α-olefin copolymer (a) may have a number average molecular weight (Mn) of 12,000 g / mol or more and 50,000 g / mol or less, a weight average molecular weight (Mw) of 100,000 g / mol or more and 250,000 g / mol or less, and a molecular weight distribution (Mw / Mn) of 3.0 or more and 20.0 or less.

[0069] Preferably, the number average molecular weight (Mn) of the first ethylene-α-olefin copolymer (a) may be 13,000 g / mol or more, 14,000 g / mol or more, or 15,000 g / mol or more, and 40,000 g / mol or less, 30,000 g / mol or less, or 28,000 g / mol or less.

[0070] In addition, the weight average molecular weight (Mw) of the first ethylene-α-olefin copolymer (a) may be 105,000 g / mol or more, 110,000 g / mol or more, or 114,000 g / mol or more, and 230,000 g / mol or less, 210,000 g / mol or less, or 200,000 g / mol or less.

[0071] Furthermore, the molecular weight distribution (Mw / Mn) of the first ethylene-α-olefin copolymer (a) may be 3.5 or more, 4.0 or more, or 4.1 or more, and 17.0 or less, 15.0 or less, or 13.1 or less.

[0072] The first ethylene-α-olefin copolymer (a) may have at least one of the above-mentioned physical properties, or may have all of the above-mentioned physical properties, and thus may exhibit excellent mechanical strength.

[0073] The first ethylene-α-olefin copolymer (a) may include at least one α-olefin selected from the group consisting of 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, and mixtures thereof, and ethylene.

[0074] Preferably, the first ethylene-α-olefin copolymer (a) may be an ethylene / 1-hexene copolymer.

[0075] When the first ethylene-α-olefin copolymer (a) is the above copolymer, the above physical properties can be more easily achieved. However, the type of the first ethylene-α-olefin copolymer (a) is not limited thereto, and various types known in the art can be used as long as they can exhibit the above physical properties.

[0076] Meanwhile, the first ethylene-α-olefin copolymer (a) having the above-mentioned physical properties may be prepared in the presence of a metallocene catalyst.

[0077] Specifically, the first ethylene-α-olefin copolymer (a) can be prepared by copolymerizing ethylene and a comonomer by passing hydrogen in the presence of a catalyst composition (containing a first metallocene compound represented by the following Chemical Formula 1 and a second metallocene compound represented by the following Chemical Formula 2 in a molar ratio of 1:1 to 1:8).

[0078] [Chemical formula 1]

[0079] (Cp 1 R a ) m (Cp 2 R b )M 2 Z 2 3-m

[0080] In Chemical Formula 1,

[0081] M 2 It is a Group 4 transition metal;

[0082] Cp 1 and Cp 2 Each is independently unsubstituted or replaced by C 1-20 Hydrocarbon-substituted cyclopentadienyl;

[0083] R a and R b are the same or different from each other and are each independently hydrogen, C 1-20 Alkyl, C 1-20 Alkoxy, C 2-20 Alkoxyalkyl, C 6-20 Aryl, C 6-20 Aryloxy, C 2-20 Alkenyl, C 7-40 Alkyl aryl, C 7-40 Arylalkyl, C 8-40 Arylene, C 2-20 alkynyl, or a substituted or unsubstituted C 2-20 Heteroaryl, precursor condition is R a and R b At least one of them is not hydrogen;

[0084] Each Z 2 are independently halogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 7-40 Alkyl aryl, C 7-40 Arylalkyl, C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkylene, substituted or unsubstituted amino, C 2-20 Alkyl alkoxy or C 7-40 Arylalkoxy; and

[0085] m is 1 or 0;

[0086] [Chemical formula 2]

[0087]

[0088] In chemical formula 2,

[0089] M 3 It is a Group 4 transition metal;

[0090] T 2 is carbon, silicon or germanium;

[0091] X 3 and X 4 are the same or different from each other and are independently halogen or C 1-20 alkyl,

[0092] R 11 To R 14 are the same or different from each other and are each independently hydrogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 6-20 Aryl, C 7-20 Alkyl aryl, C 7-20 Arylalkyl, or two or more adjacent R 11 and R 14 They are connected to each other to form a substituted or unsubstituted alicyclic ring, a substituted or unsubstituted aromatic ring, or a substituted or unsubstituted heteroaromatic ring containing at least one selected from N, O and S.

[0093] Q 3 and Q 4 are the same or different from each other and are independently C 1-20 Alkyl, C 2-20 Alkenyl, C 6-30 Aryl, or C 2-20 Alkoxyalkyl, and

[0094] R 15 C 1-20 Alkyl, C 2-20 Alkenyl, or C 6-30 Aryl.

[0095] Unless otherwise specified herein, the following terms have the following definitions.

[0096] The halogen may be fluorine (F), chlorine (Cl), bromine (Br) or iodine (I).

[0097] C 1-20 The alkyl group may be a linear alkyl group, a branched alkyl group, or a cycloalkyl group. 1-20 The alkyl group can be C 1-15 Straight chain alkyl; C 1-10 Straight chain alkyl; C 1-5 Straight chain alkyl; C 3-20 Branched alkyl or cycloalkyl; C 3-15 Branched alkyl or cycloalkyl; or C 3-10 More specifically, C 1-20 The alkyl group may be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, cyclohexyl, or the like.

[0098] C 2-20 The alkenyl group may be a straight chain alkenyl group, a branched chain alkenyl group or a cycloalkenyl group. 2-20 The alkenyl group can be C 2-20 Straight chain alkenyl, C 2-10 Straight chain alkenyl, C 2-5 Straight chain alkenyl, C 3-20 Branched alkenyl, C 3-15 Branched alkenyl, C 3-10 Branched alkenyl, C 5-20 Cycloalkenyl or C 5-10 More specifically, C 2-20 The alkenyl group may be ethenyl, propenyl, butenyl, pentenyl, cyclohexenyl, or the like.

[0099] C 6-20 The aryl group may be a monocyclic, bicyclic or tricyclic aromatic hydrocarbon, including a monocyclic or fused aryl group. More specifically, C 6-20 The aryl group may be phenyl, biphenyl, naphthyl, anthracenyl, phenanthrenyl, fluorenyl or the like.

[0100] C 7-40 The alkylaryl group may be a substituent in which at least one hydrogen on the aryl group is replaced by an alkyl group. 7-40 The alkylaryl group may be methylphenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, n-butylphenyl, isobutylphenyl, tert-butylphenyl, cyclohexylphenyl, or the like.

[0101] C 7-40 The arylalkyl group may include a substituent in which at least one hydrogen atom of the alkyl group is replaced by an aryl group. 7-40 Arylalkyl may be benzyl, phenylpropyl or phenylhexyl, and the like.

[0102] C 6-20 The aryloxy group may be a phenoxy group, a biphenyloxy group, a naphthoxy group, or the like, but the present invention is not limited thereto.

[0103] C 1-20 The alkoxy group may be a methoxy group, an ethoxy group, a phenoxy group, a cyclohexyloxy group, or the like, but the present invention is not limited thereto.

[0104] C 2-20 The alkoxyalkyl group may be a functional group in which at least one hydrogen of the alkyl group is replaced by an alkoxy group, specifically, it may be an alkoxyalkyl group such as methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl, tert-butoxyhexyl, etc., but the present invention is not limited thereto.

[0105] C 1-20 Alkylsilyl or C 1-20 The alkoxysilyl group is a functional group in which 1 to 3 hydrogens of -SiH3 are replaced by 1 to 3 of the above-mentioned alkyl or alkoxy groups, and specifically, it can be an alkylsilyl group, such as methylsilyl, dimethylsilyl, trimethylsilyl, dimethylethylsilyl, diethylmethylsilyl, dimethylpropylsilyl; an alkoxysilyl group, such as methoxysilyl, dimethoxysilyl, trimethoxysilyl or dimethoxyethoxysilyl; or an alkoxyalkylsilyl group, such as methoxydimethylsilyl, diethoxymethylsilyl, dimethoxypropylsilyl, etc., but the present invention is not limited thereto.

[0106] C 1-20 The silylalkyl group is a functional group in which at least one hydrogen in the alkyl group is replaced by a silyl group, and specifically may be -CH2-SiH3, methylsilylmethyl or dimethylethoxysilylpropyl, but the present invention is not limited thereto.

[0107] Sulfonate groups have the structure -O-SO2-R', where R' can be C 1-20 Specifically, C 1-20 The sulfonate group may be a methanesulfonate group, a phenylsulfonate group, or the like, but the present invention is not limited thereto.

[0108] A heteroaryl group is a C 2-20 Heteroaryl includes monocyclic or condensed heteroaryl. Specifically, it can be xanthene, thioanthene, thienyl, furanyl, pyrrolyl, imidazolyl, thiazolyl, oxazolyl, oxadiazolyl, triazolyl, pyridyl, bipyridyl, pyrimidyl, triazinyl, acridinyl, pyridazinyl, pyrazinyl, quinolyl, quinazolinyl, quinazolinyl, quinazolinyl, phthalazinyl, pyridine-pyrimidinyl, pyridine-pyrazinyl, pyrazine-pyrazinyl, isoquinolyl, indolyl, carbazolyl, benzoxazolyl, benzimidazolyl, benzothiazolyl, benzocarbazolyl, benzothienyl, dibenzothienyl, benzofuranyl, o-phenanthroline, isoxazolyl, thiadiazolyl, phenothiazinyl, dibenzofuranyl, but the present invention is not limited thereto.

[0109] In addition, the Group 4 transition metal may be titanium (Ti), zirconium (Zr), hafnium (Hf) or Specifically, titanium (Ti), zirconium (Zr), or hafnium (Hf). More specifically, it may be zirconium (Zr) or hafnium (Hf), but is not limited thereto.

[0110] In addition, the Group 13 element may be boron (B), aluminum (Al), gallium (Ga), indium (In), or thallium (Tl), specifically, boron (B) or aluminum (Al). However, it is not limited thereto.

[0111] The above-mentioned substituents may be optionally substituted by one or more substituents selected from the group consisting of a hydroxyl group, a halogen group, an alkyl group or an alkenyl group, an aryl group, an alkoxy group, an alkyl group or an alkenyl group, an aryl group, an alkoxy group containing at least one heteroatom of Groups 14 to 16, a silyl group, an alkylsilyl group or an alkoxysilyl group, a phosphino group, a phosphide group, a sulfonate group, and a sulfone group, within the range of exhibiting the same or similar effects as the desired effects.

[0112] In addition, "two adjacent substituents are connected to each other to form an aliphatic ring or an aromatic ring" means that the atoms of the two substituents and the atoms to which the two substituents are bonded are connected to each other to form a ring. Specifically, -NR9R 10 R9 and R 10 Examples of the groups connected to form an alicyclic ring may include piperidinyl, -NR9R 10 R9 and R 10 Examples of groups connected to each other to form an aromatic ring may include a pyrrolyl group.

[0113] In the catalyst composition, the first metallocene compound represented by Chemical Formula 1 is a compound containing Cp 1 and Cp 2 The non-crosslinked compounds of the ligands are advantageous for producing mainly low molecular weight copolymers with low SCB (short chain branch) content.

[0114] Specifically, in Chemical Formula 1, Cp 1 and Cp 2 The ligands may be the same or different from each other, and may each be liganded by one or more, or 1 to 3 C 1-10 Alkyl substituted cyclopentadienyl. 1 and Cp 2 The ligand has a non-covalent electron pair that can act as a Lewis base, thus achieving high polymerization activity. 1 and Cp 2 The ligands are cyclopentadienyl groups with relatively small steric hindrance, so they can exhibit high polymerization activity and low hydrogen reactivity, so low molecular weight polyethylene can be polymerized with high activity.

[0115] In addition, Cp 1 and Cp 2 The ligand can easily control the properties of the prepared polyethylene, such as chemical structure, molecular weight, molecular weight distribution, mechanical properties and transparency, by adjusting the degree of steric hindrance effect according to the type of substituted functional group. 1 and Cp 2 The ligands are substituted with R a and R b , where R a and R b are the same as or different from each other and are each independently hydrogen, C 1-20 Alkyl, C 2-20 Alkoxyalkyl, C 7-40 an arylalkyl group, or a substituted or unsubstituted C 2-12 Heteroaryl, more specifically C 1-10 Alkyl, C 2-10 Alkoxyalkyl, C 7-20 Arylalkyl or a substituted or unsubstituted C 4-12 Heteroaryl.

[0116] In addition, M 2 Z 2 3-m Exists in Cp 1 and Cp 2 Between ligands, M 2 Z 2 3-m This may affect the storage stability of the metal complex. In order to ensure this effect, Z 1 can be independently halogen or C 1-20 Alkyl, more specifically F, Cl, Br or I. In addition, M 2 Each independently may be Ti, Zr or Hf; Zr or Hf; or Zr.

[0117] The first metallocene compound may be a compound as follows: wherein Cp 1 and Cp 2 are unsubstituted or substituted cyclopentadienyl, R a and R b are independently hydrogen, C 1-10 Alkyl, C 2-10 Alkoxyalkyl, or C 7-20 Arylalkyl, where R a and R b At least one of the substituents is an alkoxyalkyl group, such as tert-butoxyhexyl, more specifically, the substituent -(CH2) p -OR c (Among them, R c is a straight or branched alkyl group having 1 to 6 carbon atoms, and p is an integer from 2 to 4). In addition, compared with other Cp-based catalysts that do not contain the above-mentioned substituents when preparing polyethylene using comonomers, this case shows a lower conversion rate for the comonomer, so that a low molecular weight polyethylene with a controlled degree of copolymerization or comonomer distribution can be prepared. In addition, when the first metallocene compound having the above-mentioned structure is supported on a carrier, -(CH2) in the substituent p -OR c The groups can form covalent bonds through close interaction with silanol groups on the surface of silica as a support, thus making stable supported polymerization possible.

[0118] The first metallocene compound represented by Chemical Formula 1 may be a compound represented by one of the following structural formulas, but is not limited thereto:

[0119]

[0120] The first metallocene compound represented by Chemical Formula 1 may be synthesized by applying a known reaction, and a more detailed synthesis method may be understood with reference to Examples.

[0121] Meanwhile, in one embodiment of the present invention, the second metallocene compound represented by Chemical Formula 2 comprises an aromatic ring compound containing a cyclopentadienyl group or a derivative thereof and a nitrogen atom, and has the aromatic ring compound and the nitrogen atom connected via T as a bridge group. 2 Q 3 Q 4 When the second metallocene compound having such a specific structure is used in the polymerization reaction of ethylene / 1-hexene copolymer, it can show higher activity and copolymerizability and can provide an olefin copolymer with a higher molecular weight.

[0122] In particular, the second metallocene compound represented by Chemical Formula 2 has a well-known CGC (constrained geometry catalyst) structure, so the incorporation amount of the comonomer is excellent, and the distribution of the comonomer is controlled by the electronic and stereo characteristics of the ligand. These characteristics can control the ASL (average ethylene sequence length), increase the medium molecular weight region and the high molecular weight region in the molecular weight distribution, thereby increasing the tethered molecule fraction and the entanglement degree of the polymer chain. Therefore, it is easy to prepare a polyethylene resin with long-term stability and processability, as well as excellent pipe internal pressure resistance.

[0123] M of the metallocene compound represented by Chemical Formula 2 3 It may be a Group 4 transition metal, preferably titanium (Ti), zirconium (Zr) or hafnium (Hf).

[0124] Preferably, T in Chemical Formula 2 2 It may be silicon.

[0125] Preferably, X in Chemical Formula 2 3 and X 4 Each may independently be methyl or chlorine (Cl).

[0126] Preferably, R in Chemical Formula 2 11 To R 14 The same as or different from each other, and each may independently be a methyl group or a phenyl group.

[0127] Preferably, two or more adjacent R in Chemical Formula 2 11 To R 14 are connected to each other to form a substituted or unsubstituted alicyclic ring, a substituted or unsubstituted aromatic ring, or a substituted or unsubstituted heteroaromatic ring containing at least one selected from N, O and S. For example, in Chemical Formula 2, when two or more adjacent R 11 To R 14 When they are connected to form an alicyclic ring, an aromatic ring or a heteroaromatic ring, they may form a cyclopentadiene-fused indenyl, fluorenyl, benzothienyl or dibenzothienyl. In addition, the indenyl, fluorenyl, benzothienyl and dibenzothienyl may be substituted by one or more substituents.

[0128] Preferably, R in Chemical Formula 2 15 To R 16 The same as or different from each other, and may each independently be a methyl group, an ethyl group, a phenyl group, a propyl group, a hexyl group or a tert-butoxyhexyl group.

[0129] Preferably, R in Chemical Formula 2 17 It may be methyl, ethyl, n-propyl, isopropyl, n-butyl or tert-butyl.

[0130] As the second metallocene compound capable of providing a polyethylene resin having excellent long-term stability and processability and internal pressure resistance due to an increase in the medium and high molecular weight region, the metallocene compound of Chemical Formula 2 may be selected from any one of the following compounds, but the present invention is not limited thereto:

[0131]

[0132] The second metallocene compound represented by Chemical Formula 2 can be synthesized by applying known reactions. Specifically, it can be prepared by the following method: a nitrogen compound and a cyclopentadiene derivative are connected with a bridge compound to prepare a ligand compound, and then a metal precursor compound is added to perform metallization. However, the method is not limited thereto, and a more detailed synthesis method can refer to the examples.

[0133] The second metallocene compound of Chemical Formula 2 has excellent activity and can polymerize a high molecular weight polyethylene resin. In particular, even when used by supporting on a carrier, it can exhibit high polymerization activity, and thus can prepare a polyethylene resin having an ultrahigh molecular weight.

[0134] In addition, even when hydrogen is used for polymerization to prepare a polyethylene resin having both a high molecular weight and a wide molecular weight distribution, the second metallocene compound of the chemical formula 2 of the present invention exhibits low hydrogen reactivity, and thus can copolymerize an ultra-high molecular weight polyethylene resin with high activity. Therefore, even when used in combination with a catalyst having other characteristics, a polyethylene resin satisfying the high molecular weight characteristic can be prepared without deteriorating the activity, and therefore, a polyethylene resin having a wide molecular weight distribution and containing a relatively high molecular weight polyethylene resin can be easily prepared.

[0135] As described above, in the catalyst composition, the first metallocene compound represented by Chemical Formula 1 can mainly contribute to the preparation of a low molecular weight copolymer having a low SCB content, and the second metallocene compound represented by Chemical Formula 2 can mainly contribute to the preparation of a high molecular weight copolymer having a high SCB content. More specifically, the second metallocene compound in the catalyst composition has a high incorporation amount of a comonomer in a high molecular weight region of the copolymer, while the first metallocene compound has a low incorporation amount of a comonomer in a low molecular weight region of the copolymer. Therefore, a polyethylene resin having excellent heat resistance and excellent mechanical properties by having a bimodal molecular weight distribution can be prepared.

[0136] In particular, controlling the content ratio of the first metallocene compound and the second metallocene compound in the catalyst composition can help achieve the above-mentioned physical properties and further enhance the improvement effect. Specifically, when the content of the second metallocene compound in the catalyst composition is higher than that of the first metallocene compound, the content of the medium molecular weight region and the high molecular weight region in the molecule increases, thereby increasing the tethered molecule fraction and the degree of entanglement of the polymer chain, thereby optimizing the ratio of the high molecular weight region and the low molecular weight region.

[0137] Specifically, the molar ratio of the first metallocene to the second metallocene may be 1:1 to 1:8. Preferably, the molar ratio of the first metallocene to the second metallocene may be 1:1 to 1:7, 1:1 to 1:6, or 1:1 to 1:5.5. When the content of the first metallocene compound and the second metallocene compound is within the above range, the balance between the mechanical properties and the elongation of the polyethylene resin prepared therefrom is controlled. Therefore, it can maintain the same or better levels as conventional products in terms of mechanical properties, productivity and tensile stability, and can improve high shrinkage resistance, printability and transparency.

[0138] Meanwhile, the first metallocene compound and the second metallocene compound have the above structural features and can be stably supported on the carrier.

[0139] In this case, the first metallocene compound and the second metallocene compound are used in a state supported on a carrier. When used as a supported catalyst, the prepared polymer has excellent particle shape and bulk density, and the catalyst can be applied to conventional slurry polymerization, bulk polymerization and gas phase polymerization.

[0140] The support may be silica, alumina, magnesia, silica-alumina or silica-magnesia, and may generally include oxides, carbonates, sulfates or nitrates, such as Na2O, K2CO3, BaSO4, Mg(NO3)2, etc. Among the above supports, the silica support hardly releases the catalyst from the support surface during ethylene polymerization because the transition metal compound is supported by chemical bonding with reactive functional groups (e.g., siloxane groups) present on the surface of the silica support. Therefore, when polyethylene is prepared by slurry polymerization or gas phase polymerization, scaling, adhesion to the reactor wall or adhesion to each other can be minimized.

[0141] In addition, the support can be surface modified by calcination or drying process to improve support efficiency and minimize leaching and scaling. Through the above surface modification steps, the moisture on the support surface that inhibits reaction with the supported components can be removed, and the content of reactive functional groups (such as hydroxyl and siloxane groups) that can chemically bond with the supported components can be increased.

[0142] Specifically, the calcination or drying process of the carrier can be carried out in the range of the temperature at which the moisture disappears from the surface of the carrier to the temperature at which the reactive functional groups present on the surface, especially the hydroxyl groups (OH groups), are completely eliminated. Specifically, the temperature can be 150°C to 600°C, or 200°C to 500°C. When the temperature is low, below 150°C, the water removal efficiency is low, so the moisture remaining on the carrier may react with the co-catalyst, thereby reducing the carrier efficiency. When the temperature is too high, above 600°C, the pores on the surface of the carrier may be combined with each other, reducing the specific surface area, and many reactive functional groups, such as hydroxyl groups or silanol groups, may be lost from the surface, leaving only siloxane groups. Therefore, the reaction sites with the co-catalyst may be reduced, which is not preferred.

[0143] When the first metallocene compound and the second metallocene compound are supported on a carrier and the carrier is silica, the total supported amount of the first metallocene compound and the second metallocene compound may be 40 μmol or more, 80 μmol or more, and 240 μmol or less, 160 μmol or less based on 1 g of silica. When supported within the above range, appropriate supported activity may be exhibited, which may be beneficial to maintaining the activity and economic feasibility of the catalyst.

[0144] In addition, the catalyst composition may further contain a co-catalyst in terms of improving high activity and process stability.

[0145] In the hybrid supported metallocene catalyst of the present invention, the type and content of the co-catalyst additionally included are as described above, and thus specific details will be omitted.

[0146] For example, among the above compounds, more specifically, the cocatalyst may be an alkylaluminoxane-based cocatalyst, such as methylaluminoxane.

[0147] In addition, the alkylaluminoxane-based cocatalyst stabilizes the metallocene compound and acts as a Lewis acid, thereby further enhancing the catalytic activity by including a metal element capable of forming a bond with a functional group introduced into the bridging group of the second metallocene compound through Lewis acid-base interactions.

[0148] In addition, the amount of the cocatalyst used can be appropriately adjusted according to the desired performance or effect of the catalyst and the resin composition. For example, when using silica as a carrier, the cocatalyst can be loaded with an amount of more than 8 mmol, more than 10 mmol, and less than 25 mmol or less than 20 mmol based on the weight of the carrier (e.g., 1 g of silica).

[0149] In addition, the above-mentioned catalyst composition can be used alone for polymerization, or can be used in a prepolymerized state by contacting with ethylene monomer before use in a polymerization reaction. In this case, the preparation method according to an embodiment of the present invention may also include a prepolymerization step in which the catalyst composition is contacted with ethylene monomer before preparing polyethylene by polymerization reaction.

[0150] In addition, the catalyst composition may be dissolved or diluted in an aliphatic hydrocarbon solvent having 5 to 12 carbon atoms (e.g., pentane, hexane, heptane, nonane, decane and isomers thereof), an aromatic hydrocarbon solvent (e.g., toluene and benzene), or a hydrocarbon solvent substituted with chlorine (e.g., dichloromethane and chlorobenzene), and then injected. The solvent used herein is preferably used after removing a small amount of water or air as a catalyst poison by treating with a small amount of alkylaluminum. A cocatalyst may also be further used.

[0151] Meanwhile, the polymerization process may be performed by contacting ethylene and a comonomer in the presence of the above-mentioned catalyst composition. In particular, the polymerization reaction may be performed in a bimodal type using two or more reactors or in a single polymerization reactor.

[0152] The polymerization reaction may be carried out at a temperature of 25°C to 500°C, preferably 25°C to 200°C, and more preferably 50°C to 150°C. In addition, the polymerization may be carried out at a temperature of 1 kgf / cm 2 Up to 100kgf / cm 2 , preferably 1kgf / cm 2 Up to 50kgf / cm 2 , more preferably 5kgf / cm 2 to 30kgf / cm 2 under pressure.

[0153] In addition, during the copolymerization process, 1-hexene as a comonomer input may be about 4.0 wt% to about 6.0 wt% based on the total input weight of ethylene. More specifically, the input amount of 1-hexene may be 4.1 wt% or more, about 4.2 wt% or more, about 4.3 wt% or more, about 4.4 wt% or more, or about 4.5 wt% or more, and about 5.9 wt% or less, about 5.8 wt% or less, 5.6 wt% or less, about 5.4 wt% or less, about 5.2 wt% or less, or about 5.0 wt% or less.

[0154] Meanwhile, the polyethylene resin of the present invention can be prepared by copolymerizing ethylene and a comonomer in the presence of the above-mentioned catalyst composition while feeding hydrogen.

[0155] For example, hydrogen may be fed in an amount of 35 ppm to 250 ppm, 40 ppm to 200 ppm, 50 ppm to 190 ppm, 55 ppm to 180 ppm, 58 ppm to 170 ppm, or 60 ppm to 145 ppm based on the weight of ethylene.

[0156] In the step of loading the catalyst precursor onto the co-catalyst carrier, the supported catalyst may be prepared by adding the first transition metal compound and the second transition metal compound to the carrier loaded with the co-catalyst, stirring, and then further adding the co-catalyst.

[0157] In the hybrid supported metallocene catalyst of this embodiment, the amounts of the support, the co-catalyst, the support loaded with the co-catalyst and the transition metal compound may be appropriately adjusted according to the desired performance or effect of the supported catalyst.

[0158] Meanwhile, when the molar ratio of the first transition metal compound to the second transition metal compound (first transition metal compound: second transition metal compound) is less than 1:0.3, it is difficult to produce ultra-low density polyethylene due to the reduced amount of comonomer incorporation. When the ratio exceeds 1:5.5, it is difficult to reproduce the desired polymer molecular structure.

[0159] At this time, the loading amount of the metallocene compound supported on the silica carrier may be 0.01 mmol / g to 1 mmol / g based on 1 g of the carrier. That is, considering the effect of the metallocene compound on the catalyst, it is preferred to control the usage within the above range.

[0160] When preparing the hybrid supported catalyst, the reaction solvent may be a hydrocarbon solvent such as pentane, hexane and heptane; or an aromatic solvent such as benzene and toluene.

[0161] For detailed information about the preparation method of the supported catalyst, please refer to the embodiments described below. However, the preparation method of the supported catalyst is not limited to these descriptions. The preparation method can also include steps commonly performed in the technical field of the present invention, and the steps of the preparation method can be changed by commonly changeable steps.

[0162] Meanwhile, the method for preparing the polyethylene copolymer may further include the step of copolymerizing ethylene and α-olefin in the presence of the hybrid supported metallocene catalyst.

[0163] The hybrid supported catalyst can exhibit excellent loading performance, catalytic activity and high comonomer incorporation, and can produce polyethylene copolymers that can produce biaxially stretched films with excellent expandable processing area characteristics and mechanical properties.

[0164] The first ethylene-α-olefin copolymer (a) can be prepared by a slurry polymerization process using ethylene and α-olefin as raw materials in the presence of the above-mentioned hybrid supported catalyst using conventional equipment and contact technology.

[0165] The first ethylene-α-olefin copolymer (a) may be prepared by copolymerizing ethylene and α-olefin using a continuous slurry polymerization reactor, a loop slurry reactor, or the like, but the present invention is not limited thereto.

[0166] That is, in the hybrid supported metallocene catalyst of the present invention, the first metallocene compound and the second metallocene compound are supported in the above molar ratio, and due to the interaction of more than two catalysts, the processability, shrinkage and mechanical properties of the polyethylene copolymer can be further improved.

[0167] In the hybrid supported metallocene catalyst of the present invention, the support for supporting the first metallocene compound and the second metallocene compound, the additionally contained cocatalyst and the polymerization process are as described above for the first ethylene-α-olefin copolymer (a), and the specific details thereof are omitted.

[0168] The first ethylene-α-olefin copolymer (a) of the present invention can be prepared by copolymerizing ethylene and α-olefin using the above-mentioned supported metallocene catalyst.

[0169] By the above-mentioned preparation method, the first ethylene-α-olefin copolymer (a) having the above-mentioned physical properties can be prepared.

[0170] Second ethylene-α-olefin copolymer (b)

[0171] In the polyethylene composition of the present invention, the second ethylene-α-olefin copolymer (b) having excellent fluidity and excellent tensile stability and shrinkage resistance is mixed with the above-mentioned first ethylene-α-olefin copolymer (a), thereby adjusting the balance between mechanical properties and elongation. Therefore, it can impart the characteristics suitable for manufacturing a biaxially stretched film having high shrinkage resistance, printability and transparency while maintaining the same or better mechanical properties, productivity and tensile stability than conventional films.

[0172] Specifically, the density of the second ethylene-α-olefin copolymer (b) is 0.870 g / cm 3 Up to 0.920g / cm 3 Melt index (MI 2.16 , 190°C, 2.16kg load) is 3.0g / 10min to 10.0g / 10min.

[0173] Preferably, the density of the second ethylene-α-olefin copolymer (b) may be 0.880 g / cm 3 Above, 0.890g / cm 3 Above, 0.895g / cm 3 Above, 0.915g / cm 3 Below, 0.910g / cm 3 Below, or 0.905g / cm 3 the following.

[0174] In addition, the melt index (MI) of the second ethylene-α-olefin copolymer (b) 2.16 , 190°C, 2.16 kg load) can be 4.0 g / 10 min or more, 5.0 g / 10 min or more, or 5.5 g / 10 min or more, and 9.0 g / 10 min or less, 8.0 g / 10 min or less, or 7.0 g / 10 min or less.

[0175] The second ethylene-α-olefin copolymer (b) may have a number average molecular weight (Mn) of 20,000 g / mol to 50,000 g / mol, a weight average molecular weight (Mw) of 50,000 g / mol to 100,000 g / mol, and a molecular weight distribution (Mw / Mn) of 2.0 to 4.0.

[0176] Preferably, the number average molecular weight (Mn) of the second ethylene-α-olefin copolymer (b) may be 23,000 g / mol or more, 25,000 g / mol or more, or 28,000 g / mol or more, and 45,000 g / mol or less, 40,000 g / mol or less, or 35,000 g / mol or less.

[0177] Furthermore, the weight average molecular weight (Mw) of the second ethylene-α-olefin copolymer (b) may be 55,000 g / mol or more, 60,000 g / mol or more, or 65,000 g / mol or more, and 90,000 g / mol or less, 80,000 g / mol or less, or 70,000 g / mol or less.

[0178] Furthermore, the molecular weight distribution (Mw / Mn) of the second ethylene-α-olefin copolymer (b) may be 2.1 or more, 2.2 or more, or 2.3 or more, and 3.5 or less, 3.0 or less, or 2.5 or less.

[0179] The second ethylene-α-olefin copolymer (b) may have at least one of the above-mentioned physical properties, or may have all of the above-mentioned physical properties, thereby being able to exhibit excellent mechanical strength.

[0180] The second ethylene-α-olefin copolymer (b) may comprise at least one α-olefin selected from the group consisting of 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, and mixtures thereof, and ethylene.

[0181] The second ethylene-α-olefin copolymer (b) may preferably be an ethylene / 1-octene copolymer.

[0182] When the second ethylene-α-olefin copolymer (b) is the above copolymer, the above physical properties can be more easily achieved. However, the type of the second ethylene-α-olefin copolymer (b) is not limited thereto, and various types known in the art can be used as long as they can exhibit the above physical properties.

[0183] Furthermore, the second ethylene-α-olefin copolymer (b) may be prepared in the presence of a metallocene catalyst.

[0184] Specifically, the second ethylene-α-olefin copolymer (b) may be prepared by copolymerizing ethylene and a comonomer in the presence of a catalyst composition containing a metallocene compound represented by the following Chemical Formula 3:

[0185] [Chemical formula 3]

[0186]

[0187] In chemical formula 3,

[0188] M 1 It is a Group 4 transition metal;

[0189] X 1 and X 2 are the same as or different from each other, and are each independently halogen, nitro, amide, phosphine, phosphide, C1 to C30 hydrocarbon, C1 to C30 hydrocarbonoxy, C2 to C30 hydrocarbonoxy hydrocarbon, SiH3, C1 to C30 hydrocarbon (oxy) silyl, C1 to C30 sulfonate or C1 to C30 sulfone;

[0190] Z is -O-, -S-, or -NR a -, or -PR a -;

[0191] R a Any one of hydrogen, C1 to C20 hydrocarbon group, C1 to C20 hydrocarbon (oxy) silyl group, and C1 to C20 silyl hydrocarbon group;

[0192] T is

[0193] T 1 is C, Si, Ge, Sn or Pb,

[0194] Q 1 and Q 2 are the same as or different from each other and are each independently hydrogen, C1 to C30 hydrocarbon group, C1 to C30 hydrocarbon oxy group, C2 to C30 hydrocarbon oxy hydrocarbon group, -SiH3, C1 to C30 hydrocarbon (oxy) silyl group, halogen-substituted C1 to C30 hydrocarbon group and -NR b R c Any of;

[0195] R b and R c Each independently represents at least one of hydrogen and a C1 to C30 hydrocarbon group, or are connected to form an alicyclic ring or an aromatic ring; and

[0196] C 1 is any one of the ligands represented by the following chemical formulas 3a to 3d,

[0197] [Chemical formula 3a]

[0198]

[0199] [Chemical formula 3b]

[0200]

[0201] [Chemical formula 3c]

[0202]

[0203] [Chemical formula 3d]

[0204]

[0205] In Chemical Formulae 3a to 3d,

[0206] Y is O or S, and

[0207] R 1 To R 6 are the same as or different from each other, and are each independently any one of hydrogen, a C1 to C30 hydrocarbon group, and a C1 to C30 hydrocarbonoxy group.

[0208] Unless otherwise specified herein, the following terms have the following definitions.

[0209] The hydrocarbyl is a monovalent functional group after dehydrogenation from a hydrocarbon, and may include an alkyl, alkenyl, alkynyl, aryl, aralkyl, aralkenyl, aralkynyl, alkaryl, alkenaryl, alkynaryl, etc. The C1 to C30 hydrocarbyl may be a C1 to C20 or C1 to C10 hydrocarbyl. For example, the hydrocarbyl may be a straight chain, branched chain or cyclic alkyl. More specifically, the C1 to C30 hydrocarbyl may be a straight chain, branched chain or cyclic alkyl, such as a methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl and cyclohexyl; or an aryl, such as a phenyl, biphenyl, naphthyl, anthracenyl, phenanthrenyl or fluorenyl. In addition, it may be an arylalkyl such as methylphenyl, ethylphenyl, methylbiphenyl, methylnaphthyl, or an arylalkyl such as benzyl, phenethyl, biphenylmethyl, naphthylmethyl. It may also be an alkenyl group such as allyl, vinyl, propenyl, butenyl and pentenyl.

[0210] Hydrocarbyloxy is a functional group in which a hydrocarbon group is bonded to oxygen. Specifically, the C1 to C30 hydrocarbyloxy may be a C1 to C20 or a C1 to C10 hydrocarbyloxy. For example, the hydrocarbyloxy may be a straight chain, branched chain or cyclic alkyl group. More specifically, the C1 to C30 hydrocarbyloxy may be a straight chain, branched chain or cyclic alkoxy group, such as a methoxy group, an ethoxy group, a n-propoxy group, an isopropoxy group, a n-butoxy group, an isopropoxy group, a tert-butoxy group, a n-pentoxy group, a n-hexoxy group, a n-heptoxy group and a cyclohexyloxy group; or an aryloxy group, such as a phenoxy group and a naphthoxy group.

[0211] Hydrocarbyl is a functional group in which at least one hydrogen of the hydrocarbon group is replaced by at least one hydrocarbonoxy group. Specifically, the C2 to C30 hydrocarbyl may be a C2 to C20 or C2 to C15 hydrocarbyl. For example, the hydrocarbyl may be a straight chain, a branched chain or a cyclic alkyl. More specifically, the C2 to C30 hydrocarbyl may be an alkoxyalkyl, such as methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl and tert-butoxyhexyl; or an aryloxyalkyl, such as phenoxyhexyl.

[0212] Hydrocarbyl (oxy) silyl is a functional group in which 1 to 3 hydrogens of -SiH3 are replaced by 1 to 3 hydrocarbyl or hydrocarbyloxy groups. Specifically, C1 to C30 hydrocarbyl (oxy) silyl can be C1 to C20, C1 to C15, C1 to C10 or C1 to C5 hydrocarbyl (oxy) silyl. More specifically, C1 to C30 hydrocarbyl (oxy) silyl can be an alkyl silyl, such as methyl silyl, dimethyl silyl, trimethyl silyl, dimethyl ethyl silyl, diethyl methyl silyl, dimethyl propyl silyl; alkoxy silyl, such as methoxy silyl, dimethoxy silyl, trimethoxy silyl or dimethoxy ethoxy silyl; or alkoxy alkyl silyl, such as methoxy dimethyl silyl, diethoxy methyl silyl, dimethoxy propyl silyl, etc.

[0213] C1 to C20 silyl hydrocarbyl is a functional group in which at least one hydrogen of the hydrocarbyl is replaced by a silyl group. The silyl group may be -SiH3 or a hydrocarbyl (oxy) silyl group. Specifically, the C1 to C20 silyl hydrocarbyl may be a C1 to C15 or a C1 to C10 silyl hydrocarbyl group. More specifically, the C1 to C20 silyl hydrocarbyl may be a silylalkyl group, such as -CH2-SiH3; an alkylsilylalkyl group, such as a methylsilylmethyl group, a methylsilylethyl group, a dimethylsilylmethyl group, a trimethylsilylmethyl group, a dimethylethylsilylmethyl group, a diethylmethylsilylmethyl group or a dimethylpropylsilylmethyl group; or an alkoxysilylalkyl group, such as a dimethylethoxysilylpropyl group.

[0214] The halogen may be fluorine (F), chlorine (Cl), bromine (Br) or iodine (I).

[0215] The sulfonate group has the structure -O-SO2-R', where R d It may be a C1 to C30 hydrocarbon group. Specifically, the C1 to C30 sulfonate group may be a methanesulfonic acid group, a benzenesulfonic acid group, or the like.

[0216] C1 to C30 sulfone groups have -R e '-SO2-R e” The structure of R e ' and R e" They may be the same as or different from each other and may each independently be any one of C1 to C30 hydrocarbon groups. Specifically, the C1 to C30 sulfone group may be methylsulfonylmethyl, methylsulfonylpropyl, methylsulfonylbutyl, phenylsulfonylpropyl, or the like.

[0217] In the present invention, "two adjacent substituents are connected to each other to form an aliphatic ring or an aromatic ring" means that the atoms of the two substituents and the atoms connected to the two substituents are connected to each other to form a ring. Specifically, -NR b R c or NR b' R c’ R b With R c , or R b’ With R c’ Examples of groups connected to form an alicyclic ring include piperidinyl, -NR b R c or -NR b' R c’ R b and R c , or R b' and R c' Examples of groups linked to each other to form an aromatic ring include pyrrolyl.

[0218] The Group 4 transition metal may be titanium (Ti), zirconium (Zr), hafnium (Hf) or And more specifically, it may be titanium (Ti), zirconium (Zr) or hafnium (Hf). More specifically, it may be zirconium (Zr) or hafnium (Hf), but the present invention is not limited thereto.

[0219] In addition, the Group 13 element may be boron (B), aluminum (Al), gallium (Ga), indium (In), or thallium (Tl), and more specifically, may be boron (B) or aluminum (Al), but the present invention is not limited thereto.

[0220] The above-mentioned substituents may be optionally substituted by one or more substituents selected from the group consisting of hydroxyl; halogen; hydrocarbon; hydrocarbonoxy; heteroatom hydrocarbon or hydrocarbonoxy containing at least one heteroatom of Groups 14 to 16; silyl; hydrocarbon(oxy)silyl; phosphino; phosphide; sulfonate; and sulfone.

[0221] In the present invention, Refers to the bond to another substituent.

[0222] Specifically, in Chemical Formula 3, Z is -NR a -, where R a It can be a C1 to C10 hydrocarbon group. a It may be a linear or branched C1 to C6 alkyl group. More specifically, it may be a tert-butyl group.

[0223] In Chemical Formula 3, T is Where T 1 is carbon (C) or silicon (Si), Q 1 and Q 2 can each independently be hydrogen, a C1 to C30 hydrocarbon group, or a C1 to C30 hydrocarbonoxy group. 1 and Q 2 Each of Q may be a C1 to C10 hydrocarbon group or a C2 to C12 hydrocarbonoxy hydrocarbon group. 1 and Q 2 Each of Q and Q may be a C1 to C6 alkyl group, or a C1 to C6 alkyl group substituted with a C1 to C6 alkoxy group. 1 and Q 2 may be independently hydrogen, methyl, ethyl or hexyl substituted with tert-butoxy. More specifically, T 1 is silicon (Si); Q 1 and Q 2 All are methyl, or Q 1 and Q 2 One of them is a methyl group and the other is a hexyl group substituted with a tert-butoxy group.

[0224] Specifically, the metallocene compound represented by Chemical Formula 3 may be a compound represented by any one of the following Chemical Formulas 3-1 to 3-4.

[0225] [Chemical formula 3-1]

[0226]

[0227] [Chemical formula 3-2]

[0228]

[0229] [Chemical formula 3-3]

[0230]

[0231] [Chemical formula 3-4]

[0232]

[0233] In Chemical Formulas 3-1 to 3-4, M 1 , X 1 , X 2 , R a , T 1 , Q 1 , Q 2 , Y and R 1 To R 6 Same as the definition in Chemical Formula 3.

[0234] In chemical formula 3, R 1 To R 4 may be hydrogen or a C1 to C10 hydrocarbon group, R 5 and R 6 Each of R 1 To R 4 may each be hydrogen or a C1 to C10 alkyl group, and R 5 and R 6 may each be a C1 to C10 alkyl group. More specifically, R 1 To R 4 may each be hydrogen or methyl, and R 5 and R 6 It may be methyl.

[0235] In the chemical formula, 3, M 1 It may be titanium (Ti), zirconium (Zr) or hafnium (Hf), preferably titanium (Ti).

[0236] In addition, in Chemical Formula 3, X 1 and X 2 It can be halogen, C1 to C10 alkyl or C1 to C6 alkyl, specifically chlorine or methyl.

[0237] Furthermore, in Chemical Formula 3, the metallocene compound can be represented by one of the following structural formulas.

[0238]

[0239] The metallocene compound represented by the above structural formula can be synthesized by known reactions. For more detailed synthesis methods, please refer to Examples and Synthesis Examples.

[0240] As described above, the transition metal compound represented by Chemical Formula 3 used in the present invention can control the input degree of α-olefin monomer during the copolymerization process due to the structural characteristics of the catalyst and exhibit the above density, thereby having excellent fluidity and stretching processability.

[0241] In the present invention, the polymerization reaction can be carried out by continuously polymerizing ethylene and α-olefin monomers while continuously introducing hydrogen in the presence of a catalyst composition containing at least one transition metal compound represented by Chemical Formula 3. Specifically, the polymerization reaction can be carried out while introducing hydrogen at a rate of 5 cc / min to 100 cc / min.

[0242] Hydrogen can inhibit the rapid reaction of transition metal compounds in the early stage of polymerization and terminate the polymerization reaction. Therefore, by using hydrogen and adjusting its dosage, ethylene / α-olefin copolymers with narrow molecular weight distribution can be effectively produced.

[0243] For example, hydrogen can be added at 5cc / min or more, 7cc / min or more, 10cc / min or more, 15cc / min or more, or 19cc / min or more and 100cc / min or less, 50cc / min or less, 45cc / min or less, 35cc / min or less, or 29cc / min or less. When added under the above conditions, the produced ethylene / α-olefin copolymer can achieve the physical properties of the present invention.

[0244] When the rate of hydrogen addition is lower than 5 cc / min, the polymerization reaction cannot be terminated uniformly, and thus it is difficult to prepare an ethylene / α-olefin copolymer having desired physical properties. When hydrogen is added at a rate exceeding 100 cc / min, the termination reaction occurs too quickly, and thus an ethylene / α-olefin copolymer having a very low molecular weight may be produced.

[0245] In addition, the polymerization reaction can be carried out at 100° C. to 200° C., and the crystallinity distribution and molecular weight distribution of the ethylene / α-olefin copolymer can be more easily controlled by adjusting the polymerization temperature and the amount of hydrogen input. Specifically, the polymerization reaction can be carried out at 100° C. to 200° C., 120° C. to 180° C., 130° C. to 170° C., or 140° C. to 160° C., but is not limited thereto.

[0246] In the present invention, a co-catalyst may be further used in the catalyst composition to activate the transition metal compound of Chemical Formula 3. The co-catalyst is an organic metal compound containing a Group 13 metal, and specifically may include one or more selected from the following Chemical Formulas 4 to 4.

[0247] [Chemical formula 4]

[0248] R8-[Al(R7)-O] n -R9

[0249] In chemical formula 4,

[0250] R7, R8 and R9 are each independently hydrogen, halogen, C 1-20 Hydrocarbon or halogen substituted C 1-20 Hydrocarbyl, and

[0251] n is an integer greater than 2,

[0252] [Chemical formula 5]

[0253] D(R 10 )3

[0254] In Chemical Formula 5,

[0255] D is aluminum or boron, and

[0256] R 10 are independently halogen, C 1-20 Hydrocarbon, C 1-20 Hydroxyl or halogen substituted C 1-20 Hydrocarbon,

[0257] [Chemical formula 6]

[0258] [LH] + [W(A)4] - or [L] + [W(A)4] -

[0259] In Chemical Formula 6,

[0260] L is a neutral or cationic Lewis base;

[0261] H is a hydrogen atom;

[0262] W is a Group 13 element, and

[0263] A is independently C 1-20 Hydrocarbon; C 1-20 Hydrocarbyloxy; and one or more hydrogen atoms in these substituents are selected from halogen, C 1-20 Hydroxyl and C 1-20 Any of substituents substituted by one or more substituents in a hydrocarbyl(oxy)silyl group.

[0264] Specifically, in Chemical Formula 6, [LH] + It is a Bronsted acid.

[0265] For example, [LH] + is trimethylammonium; triethylammonium; tripropylammonium; tributylammonium; diethylammonium; trimethylphosphine; or triphenylphosphine, wherein [L] + It is N,N-diethylaniline; or triphenylcarbonylammonium.

[0266] In addition, in Chemical Formula 6, W may be B 3+ or Al 3+ .

[0267] The compound represented by Chemical Formula 4 may be used as an alkylating agent and an activating agent, the compound represented by Chemical Formula 5 may be used as an alkylating agent, and the compound represented by Chemical Formula 6 may be used as an activating agent.

[0268] More specifically, the compound of Chemical Formula 4 may be an alkylaluminoxane compound in which repeating units are combined in a linear, ring or network shape, and specific examples thereof may include methylaluminoxane (MAO), ethylaluminoxane, isobutylaluminoxane or tert-butylaluminoxane, etc. Non-limiting examples of the compound represented by Chemical Formula 4 may include methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, tert-butylaluminoxane, etc.

[0269] In addition, non-limiting examples of the compound represented by Chemical Formula 5 may include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylaluminum chloride, triisopropylaluminum, tri-sec-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylmethoxyaluminum, dimethylethoxyaluminum, and the like.

[0270] In addition, non-limiting examples of the compound represented by Chemical Formula 6 may include trimethylammonium tetrakis(pentafluorophenyl)borate, triethylammonium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium n-butyltri(pentafluorophenyl)borate, N,N-dimethylanilinium benzyltri(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(4-(tert-butyldimethylsilyl)-2,3,5,6-tetrafluorophenyl)borate, N,N-dimethylanilinium tetrakis(4-(triisopropylsilyl)-2,3,5,6-tetrafluorophenyl)borate, N,N-dimethylanilinium tetra(pentafluorophenyl)borate, N,N-dimethylanilinium pentafluorophenoxytris(pentafluorophenyl)borate, N,N-dimethyl-2,4,6-trimethylanilinium tetra(pentafluorophenyl)borate, trimethylammonium tetra(2,3,4,6-tetrafluorophenyl)borate, N,N-dimethylanilinium tetra(2,3,4,6-tetrafluorophenyl)borate, hexadecyldimethylammonium tetra(pentafluorophenyl)borate, N-methyl-N-dodecylanilinium tetra(pentafluorophenyl)borate or methyldi(dodecyl)ammonium tetra(pentafluorophenyl)borate, etc.

[0271] Among the above compounds, the cocatalyst may more specifically be an alkylaluminoxane-based cocatalyst, such as methylaluminoxane.

[0272] The amount of the co-catalyst can be appropriately adjusted according to the desired physical properties or effects of the hybrid supported metallocene catalyst.

[0273] An appropriate amount of the co-catalyst may be used to fully activate the transition metal compound of Chemical Formula 3. The amount of the co-catalyst may be appropriately adjusted according to the desired physical properties or effects of the hybrid supported metallocene catalyst.

[0274] In the present invention, the transition metal compound of Chemical Formula 3 may be used in a state of being supported on a carrier.

[0275] When the transition metal compound of Chemical Formula 3 is loaded on a carrier, the weight ratio of the transition metal compound to the carrier may be 1:10 to 1:1000, more specifically, 1:10 to 1:500. When the carrier and the transition metal compound are contained in the above weight ratio, an optimal shape may be exhibited. In addition, when the co-catalyst is loaded on a carrier, the weight ratio of the co-catalyst to the carrier may be 1:1 to 1:100, more specifically, 1:1 to 1:50. When the content of the co-catalyst and the carrier is within the above weight ratio range, the activity of the catalyst may be improved, and the microstructure of the polymer to be produced may be optimized.

[0276] Meanwhile, the carrier may be silicon dioxide, aluminum oxide, magnesium oxide or a mixture thereof, and may also be used in a state where highly reactive hydroxyl groups or siloxane groups are present on the surface of these materials after high temperature drying to remove surface moisture. In addition, the carrier after high temperature drying generally contains oxides, carbonates, sulfates and nitrates, such as Na2O, K2CO3, BaSO4, Mg(NO3)2, etc.

[0277] The drying temperature of the carrier may preferably be about 200° C. to 800° C., more preferably about 300° C. to 600° C., and most preferably about 300° C. to 400° C. If the drying temperature of the carrier is lower than 200° C., surface moisture may react with the co-catalyst due to excess moisture. If it is higher than 800° C., pores on the surface of the carrier may be combined to reduce the surface area, and a large number of hydroxyl groups may be lost on the surface to leave only siloxane groups, thereby reducing the reaction sites with the co-catalyst, which is not preferred.

[0278] The amount of hydroxyl groups on the surface of the carrier may preferably be 0.1 mmol / g to 10 mmol / g, and more preferably 0.5 mmol / g to 5 mmol / g. The amount of hydroxyl groups on the surface of the carrier may be controlled according to the preparation method and conditions of the carrier, or drying conditions (e.g., temperature, time, vacuum, spray drying, etc.).

[0279] In addition, an organoaluminum compound may be added during the polymerization reaction to remove moisture from the reactor, and the polymerization reaction may be carried out in the presence of the organoaluminum compound. Specific examples of such organoaluminum compounds may include trialkylaluminum, dialkylaluminum halides, alkylaluminum dihalides, dialkylaluminum hydrides, or alkylaluminum sesquihalides. More specific examples may include Al(C2H5)3, Al(C2H5)2H, Al(C3H7)3, Al(C3H7)2H, Al(i-C4H9)2H, Al(C8H 17 )3、Al(C 12 H 25 )3、Al(C2H5)(C 12 H 25 )2、Al(i-C4H9)(C 12 H 25 )2, Al(i-C4H9)2H, Al(i-C4H9)3, (C2H5)2AlCl, (i-C3H9)2AlCl, (C2H5)3A l2 Cl3, etc. These organoaluminum compounds can be added to the reactor continuously, and about 0.1 mol to 10 mol of the organoaluminum compound can be added to each 1 kg of reaction medium added to the reactor to fully remove moisture.

[0280] In addition, the polymerization pressure may be about 1 Kgf / cm 2 To about 100Kgf / cm 2 , preferably about 1Kgf / cm 2 To about 50Kgf / cm 2 , more preferably, about 5Kgf / cm 2 To about 30Kgf / cm 2 .

[0281] In addition, when the transition metal compound is used in a state supported on a carrier, the transition metal compound may be dissolved or diluted in an aliphatic hydrocarbon solvent having 5 to 12 carbon atoms (e.g., pentane, hexane, heptane, nonane, decane and isomers thereof), an aromatic hydrocarbon solvent (e.g., toluene and benzene), or a chlorine-substituted hydrocarbon solvent (e.g., dichloromethane and chlorobenzene), and then added. The solvent used herein is preferably used after removing a small amount of water or air as a catalyst poison by treating with a small amount of alkylaluminum. A cocatalyst may also be further used.

[0282] The second ethylene-α-olefin copolymer (b) can be prepared by copolymerizing ethylene and an α-olefin using the above-mentioned metallocene catalyst.

[0283] By the above preparation method, the second ethylene-α-olefin copolymer (b) having the above physical properties can be prepared.

[0284] Biaxially stretched film

[0285] The polyethylene composition having the above-mentioned physical properties can stably form a biaxially stretched film having high shrinkage resistance, printability and transparency while maintaining excellent mechanical properties, productivity and stretching stability.

[0286] Meanwhile, the biaxially stretched film may be produced by a conventional film production method except for using the above-mentioned polyethylene composition.

[0287] For example, in order to produce the polyethylene biaxially stretched film of the present invention, a polyethylene composition sheet having a thickness of 0.75 mm can be prepared using a laboratory extruder line manufactured by Bruckner (L / D ratio: 42, screw diameter: 25 mm, melt / T die temperature: 220°C). Thereafter, a polyethylene biaxially stretched film can be prepared by biaxially stretching a polyethylene composition sheet having a length and width of 90 mm×90 mm using a KARO 5.0 device. The specific method and conditions are shown in Test Example 3 described later.

[0288] In addition, in addition to the above-mentioned polyethylene copolymer, the polyethylene biaxially stretched film of the present invention may also contain additives known in the art. Specifically, such additives may include solvents, heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, metal deactivators, fillers, reinforcing agents, plasticizers, lubricants, emulsifiers, pigments, fluorescent whitening agents, flame retardants, antistatic agents, foaming agents, etc. The type of additive is not particularly limited, and conventional additives known in the art can be used.

[0289] The polyethylene biaxially stretched film according to one embodiment of the present invention prepared by the above method may have improved performance, excellent expandable processing area characteristics, and mechanical properties.

[0290] The haze of the biaxially stretched polyethylene film measured according to ASTM 1003 may be 0% or more, 0.5% or more, 1.0% or more, 1.5% or more, or 1.6% or more, but less than 2.0% or less than 1.9%.

[0291] The gloss 45° of the biaxially stretched polyethylene film measured according to ASTM 2457 may be 80 GU or more, or 80 GU to 100 GU, preferably 85 GU or more, 88 GU or more, 90 GU or more, or 93 GU or more.

[0292] In addition, the polyethylene biaxially stretched film also has excellent stretchability and stretching stability, so its MD stretching ratio can be greater than 4 times, or 5 times or more, and its TD stretching ratio can be greater than 6 times, or 7 times or more.

[0293] Measured according to ASTM D 882 standard, the tensile strength of the polyethylene biaxially stretched film in the MD direction can be greater than 100 MPa, greater than 110 MPa, greater than 120 MPa, and less than 150 MPa, and the tensile strength in the TD direction can be greater than 180 MPa, greater than 190 MPa, or greater than 200 MPa, and less than 250 MPa.

[0294] Therefore, the average value of the MD tensile strength and the TD tensile strength of the biaxially stretched film measured according to ASTM D 882 may be 130 MPa or more, preferably 140 MPa or more, 150 MPa or more, or 160 MPa or more, and 200 MPa or less.

[0295] Furthermore, the tensile modulus of the biaxially stretched polyethylene film in the MD direction may be 600 MPa or more, or 645 MPa or more and 1000 MPa or less, and the tensile modulus in the TD direction may be 800 MPa or more, or 900 MPa or more and 1500 MPa or less.

[0296] Therefore, the average value of the MD tensile modulus and the TD tensile modulus of the biaxially stretched film measured according to ASTM D 882 may be 700 MPa or more, preferably 750 MPa or more, 780 MPa or more, or 794.5 MPa or more, and 1000 MPa or less.

[0297] The polyethylene biaxially stretched film may have a tensile elongation of 150% to 250%, or 160% to 230% in MD, and a tensile elongation of 50% to 100%, or 65% to 90% in TD, measured according to ASTM D 882.

[0298] Measured according to ASTM 1922, the tear strength of the polyethylene biaxially stretched film in the MD direction may be 6 N / mm to 13.1 N / mm, and the tear strength in the TD direction may be 1.6 N / mm to 6.7 N / mm.

[0299] In addition, the puncture strength of the polyethylene biaxially stretched film may be 300 N / mm or more measured according to EN 14477. Preferably, the puncture strength may be 320 N / mm or more, 340 N / mm or more, or 357 N / mm or more and 400 N / mm or less.

[0300] In the present invention, the physical properties of the biaxially stretched film can be measured according to the above standards, and the specific method is described in Test Example 3 below.

[0301] In the present invention, a first ethylene-α-olefin copolymer having excellent fluidity to impart stretchability is mixed with a second ethylene-α-olefin copolymer having excellent mechanical properties, so that the balance between mechanical properties and elongation can be adjusted. Therefore, a biaxially stretched film having high shrinkage resistance, printability and transparency while maintaining excellent mechanical properties, productivity and stretching stability can be stably manufactured.

[0302] [Beneficial Effects]

[0303] The polyethylene of the present invention has an excellent effect in producing a biaxially stretched film having high shrinkage resistance, printability and transparency while maintaining excellent mechanical properties, productivity and stretching stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0304] Figure 1 The results of tensile tests on sheet specimens having a thickness of 1 mm at a tensile rate of 500% / min at room temperature (25° C.) according to ASTM D638 are shown to measure the natural draw ratio (NDR) of the polyethylene compositions of Examples and Comparative Examples, and

[0305] Figure 2 The results of a tensile test performed on a sheet specimen having a thickness of 1 mm at a tensile rate of 1000% / min at 120° C. according to ASTM D638 standard are shown to measure the elongation at break of the polyethylene compositions of Examples and Comparative Examples. DETAILED DESCRIPTION

[0306] Hereinafter, embodiments of the present invention will be described in more detail in the following examples. However, the following examples are provided only for illustration and are not intended to limit the present invention.

[0307] Example

[0308] <Preparation of Metallocene Compound>

[0309] Synthesis example 1

[0310]

[0311] t-Bu-O-(CH2)6-Cl was prepared using 6-chlorohexanol according to the method shown in Tetrahedron Lett. 2951 (1988), and reacted with Na(C5H5)[NaCp] to obtain t-Bu-O-(CH2)6-C5H5 (yield 60%, bp 80℃ / 0.1mmHg).

[0312] Then, t-Bu-O-(CH2)6-C5H5 was dissolved in tetrahydrofuran (THF) at -78°C, and n-BuLi was slowly added thereto. Thereafter, it was heated to room temperature and reacted for 8 hours. The above-synthesized lithium salt solution was slowly added to a suspension of ZrCl4(THF)2 (170 g, 4.50 mmol) / THF (30 mL) at -78°C, and further reacted at room temperature for about 6 hours. All volatiles were dried under vacuum, and the resulting oily liquid material was filtered by adding hexane solvent. The filtered solution was dried under vacuum, and hexane was added at low temperature (-20°C) to obtain a precipitate. The obtained precipitate was filtered at low temperature to obtain a [t-Bu-O-(CH2)6-C5H4]2ZrCl2 compound in the form of a white solid (yield 92%).

[0313] 1 H-NMR (300MHz, CDCl3): δ6.28 (t, J = 2.6 Hz, 2H), 6.19 (t, J = 2.6 Hz, 2H), 3.31 (t, 6.6 Hz, 2H), 2.62 (t, J = 8 Hz), 1.7-1.3 (m, 8H), 1.17 (s, 9H).

[0314] 13 C-NMR(CDCl3): δ135.09,116.66,112.28,72.42,61.52,30.66,30.31,30.14,29.18,27.58,26.00.

[0315] Synthesis example 2

[0316]

[0317] Add 50g of Mg to a 10L reactor at room temperature, followed by 300mL of THF. Add 0.5g of I2, and maintain the reactor temperature at 50°C. After the reactor temperature stabilizes, add 250g of 6-tert-butoxyhexyl chloride to the reactor at a rate of 5mL / min using a feed pump. It was observed that the reactor temperature rose by 4°C to 5°C with the addition of 6-tert-butoxyhexyl chloride. Stir for 12 hours while continuously adding 6-tert-butoxyhexyl chloride. After reacting for 12 hours, a black reaction liquid was obtained. Take 2mL of the black solution and add water thereto to obtain an organic layer. By 1 H-NMR confirmed that the organic layer was 6-tert-butoxyhexane. This confirmed that the Grignard reaction proceeded smoothly. Therefore, 6-tert-butoxyhexylmagnesium chloride was synthesized.

[0318] 500g of MeSiCl3 and 1L of THF were added to the reactor, and then the reactor temperature was cooled to -20°C. 560g of the above-synthesized 6-tert-butoxyhexylmagnesium chloride was added to the reactor at a rate of 5mL / min using a feed pump. After the feeding of the Grignard reagent was completed, the mixture was stirred for 12 hours while the temperature of the reactor was slowly raised to room temperature. After 12 hours of reaction, it was confirmed that a white MgCl2 salt was generated. Then, 4L of hexane was added thereto, and the salt was removed by labdori to obtain a filtered solution. After the filtered solution was added to the reactor, the hexane was removed at 70°C to obtain a light yellow liquid. By 1 H-NMR confirmed that the obtained liquid was methyl(6-tert-butoxyhexyl)dichlorosilane.

[0319] 1 H-NMR (300MHz, CDCl3): δ3.3(t,2H),1.5(m,3H),1.3(m,5H),1.2(s,9H),1.1(m,2H),0.7(s,3H).

[0320] 1.2 mol (150 g) of tetramethylcyclopentadiene and 2.4 L of THF were added to the reactor, and then the reactor temperature was cooled to -20 ° C. 480 mL of n-BuLi was added to the reactor at a rate of 5 mL / min using a feed pump. After the addition of n-BuLi, the mixture was stirred for 12 hours while the temperature of the reactor was slowly raised to room temperature. After 12 hours of reaction, an equal amount of methyl (6-tert-butoxyhexyl) dichlorosilane (326 g, 350 mL) was quickly added to the reactor. The mixture was stirred for 12 hours while the temperature of the reactor was slowly raised to room temperature. Then, the reactor temperature was cooled to 0 ° C again and 2 equivalents of t-BuNH2 were added. The mixture was stirred for 12 hours while the temperature of the reactor was slowly raised to room temperature. After 12 hours of reaction, THF was removed. After that, 4 L of hexane was added and the salt was removed by labdori to obtain a filtered solution. The filtered solution was added to the reactor again, and the hexane was removed at 70 ° C to obtain a yellow solution. By 1 H-NMR confirmed that the yellow solution obtained above was methyl(6-tert-butoxyhexyl)(tetramethyl CpH)tert-butylaminosilane.

[0321] TiCl3(THF)3 (10 mmol) was quickly added to the dilithium salt of the ligand, which was synthesized from n-BuLi and synthesized dimethyl(tetramethylCpH)tert-butylaminosilane in THF solution at -78°C. The reaction solution was stirred for 12 hours while slowly heating it from -78°C to room temperature. After stirring for 12 hours, an equal amount of PbCl2 (10 mmol) was added to the reaction solution at room temperature, which was then stirred for 12 hours. After stirring for 12 hours, a dark black solution with a blue tint was obtained. THF was removed from the obtained reaction solution, and hexane was then added to filter the product. Hexane was removed from the filtered solution, and then the product was filtered by 1 H-NMR confirmed that the product was (tBu-O-(CH2)6)(CH3)Si(C5(CH3)4)(tBu-N)TiCl2([methyl(6-tert-butoxyhexyl)silyl(η5-tetramethylCp)(tert-butylamido)]TiCl2).

[0322] 1 H-NMR (300MHz, CDCl3): δ3.3(s,4H),2.2(s,6H),2.1(s,6H),1.8~0.8(m),1.4(s,9H),1.2(s,9H),0.7(s,3H).

[0323] Synthesis example 3

[0324] (1) Preparation of ligand A

[0325] 1-Benzothiophene solution was prepared by dissolving 4.0 g (30 mmol) 1-benzothiophene in THF. Then, 14 mL n-BuLi solution (36 mmol, 2.5 M hexane solution) and 1.3 g (15 mmol) CuCN were added to the 1-benzothiophene solution. Then, 3.6 g (30 mmol) of tigloyl chloride were slowly added to the above solution at -80 ° C, and the resulting solution was stirred at room temperature for about 10 hours. Then, 10% HCl was poured into the above solution to quench the reaction, and the organic layer was separated with dichloromethane to obtain (2E)-1-(1-benzothiophene-2-yl)-2-methyl-2-butan-1-one in the form of a beige solid.

[0326]

[0327] 1 H NMR(CDCl3):7.85-7.82(m,2H),7.75(m,1H),7.44-7.34(m,2H),6.68(m,1H),1.99(m,3H),1.92(m,3H)

[0328] 34 mL of sulfuric acid was slowly added to a solution of 5.0 g (22 mmol) of the above-prepared (2E)-1-(1-benzothiophene-2-yl)-2-methyl-2-butan-1-one dissolved in 5 mL of chlorobenzene while vigorously stirring. The solution was then stirred at room temperature for about 1 hour. Ice water was then poured into the solution, and the organic layer was separated with an ether solvent to obtain 4.5 g of 1,2-dimethyl-1,2-dihydro-3H-benzo[b]cyclopenta[d]thiophene-3-one (yield 91%) in the form of a yellow solid.

[0329]

[0330] 1 H NMR(CDCl3):7.95-7.91(m,2H),7.51-7.45(m,2H),3.20(m,1H),2.63(m,1H),1.59(d,3H),1.39(d,3H).

[0331] 570 mg (15 mmol) of NaBH4 was added to a solution obtained by dissolving 2.0 g (9.2 mmol) of 1,2-dimethyl-1,2-dihydro-3H-benzo[b]cyclopenta[d]thiophene-3-one in a mixed solvent of 20 mL of THF and 10 mL of methanol at 0°C. Then, the solution was stirred at room temperature for about 2 hours. Thereafter, HCl was added to the solution to adjust the pH to 1, and the organic layer was separated with an ether solvent to obtain an alcohol intermediate.

[0332] A solution was prepared by dissolving the alcohol intermediate in toluene. Then, 190 mg (1.0 mmol) of p-toluenesulfonic acid was added to the solution and refluxed for about 10 minutes. The resulting reaction mixture was separated by column chromatography to obtain 1.8 g (9.0 mmol, 98% yield) of 1,2-dimethyl-3H-benzo[b]cyclopenta[d]thiophene (ligand A) in the form of an orange-brown liquid.

[0333]

[0334] 1 H NMR(CDCl3):7.81(d,1H),7.70(d,1H),7.33(t,1H),7.19(t,1H),6.46(s,1H),3.35(q,1H),2.14(s,3H),1.14(d,3H).

[0335] (2) Preparation of ligand B

[0336] 13 mL (120 mmol) of tert-butylamine and 20 mL of ether solvent were added to a 250 mL Schlenk flask, and 16 g (60 mmol) of (6-tert-butoxyhexyl)dichloro(methyl)silane and 40 mL of ether solvent were added to another 250 mL Schlenk flask to prepare a tert-butylamine solution and a (6-tert-butoxyhexyl)dichloro(methyl)silane solution, respectively. The tert-butylamine solution was then cooled to -78°C, and the (6-tert-butoxyhexyl)dichloro(methyl)silane solution was slowly injected into the cooled solution, followed by stirring at room temperature for about 2 hours. The resulting white suspension was filtered to obtain 1-(6-(tert-butoxy)hexyl)-N-(tert-butyl)-1-chloro-1-methylsilaneamine (ligand B) in the form of an ivory liquid.

[0337]

[0338] 1 H NMR (CDCl3): 3.29 (t, 2H), 1.52-1.29 (m, 10H), 1.20 (s, 9H), 1.16 (s, 9H), 0.40 (s, 3H).

[0339] (3) Cross-linking of ligands A and B

[0340] 1.7 g (8.6 mmol) of 1,2-dimethyl-3H-benzo[b]cyclopenta[d]thiophene (ligand A) was added to a 250 mL Schlenk flask, and then 30 mL of THF was added to prepare a ligand A solution. After the ligand A solution was cooled to -78 ° C, 3.6 mL (9.1 mmol, 2.5 M in hexane) of n-BuLi solution was added to the ligand A solution. Then, the mixture was stirred at room temperature overnight to obtain a purple-brown solution. The solvent of the purple-brown solution was replaced with toluene, and a solution of 39 mg (0.43 mmol) of CuCN dispersed in 2 mL of THF was injected thereto to prepare solution A.

[0341] At the same time, solution B prepared by injecting 1-(6-(tert-butoxy)hexyl)-N-(tert-butyl)-1-chloro-1-methylsilaneamine (ligand B) and toluene into a 250 mL Schlenk flask was cooled to -78°C. Solution A prepared above was slowly injected into the cooled solution B. Then, the mixture of solutions A and B was stirred at room temperature overnight. Thereafter, the resulting solid was removed by filtration to obtain 4.2 g (>99% yield) of 1-(6-(tert-butoxy)hexyl)-N-(tert-butyl)-1-(1,2-dimethyl-3H-benzo[b]cyclopenta[d]thiophene-3-yl)-1-methylsilaneamine (cross-linked product of ligands A and B) in the form of a brown viscous liquid.

[0342]

[0343] To confirm the structure of the cross-linked product of ligands A and B, the cross-linked product was lithiated at room temperature, and then the H-NMR spectrum was obtained using a sample dissolved in a small amount of pyridine-D5 and CDCl3.

[0344] 1 H NMR (pyridine-D5 and CDCl3): 7.81 (d, 1H), 7.67 (d, 1H), 7.82-7.08 (m, 2H), 3.59 (t, 2H), 3.15 (s, 6H), 2.23-1.73 (m, 10H), 2.15 (s, 9H), 1.91 (s, 9H), 1.68 (s, 3H).

[0345] (4) Preparation of transition metal compounds

[0346] 4.2 g (8.6 mmol) of 1-(6-(tert-butoxy)hexyl)-N-(tert-butyl)-1-(1,2-dimethyl-3H-benzo[b]cyclopenta[d]thiophene-3-yl)-1-methylsilaneamine (a cross-linked product of ligands A and B) was added to a 250 mL Schlenk flask, and 14 mL of toluene and 1.7 mL of n-hexane were added to the flask to dissolve the cross-linked product. The solution was cooled to -78°C, and then 7.3 mL (18 mmol, 2.5 M hexane solution) was injected into the cooled solution. Thereafter, the solution was stirred at room temperature for about 12 hours. Then, 5.3 mL (38 mmol) of trimethylamine was added to the solution, and then stirred at about 40°C for about 3 hours to prepare solution C.

[0347] At the same time, 2.3 g (8.6 mmol) of TiCl4 (THF)2 and 10 mL of toluene were added to a separately prepared 250 mL Schlenk flask to prepare a solution D in which TiCl4 (THF)2 was dispersed in toluene. The solution C prepared before the solution D was slowly injected at -78 ° C, and the mixture of the solutions C and D was stirred at room temperature for about 12 hours. Afterwards, the solution was decompressed to remove the solvent, and the obtained solute was dissolved in toluene. Then, the solid insoluble in toluene was removed by filtration, and the solvent was removed from the filtrate to obtain 4.2 g (yield 83%) of the transition metal compound in the form of a brown solid.

[0348]

[0349] 1 H NMR(CDCl3):8.01(d,1H),7.73(d,1H),7.45-7.40(m,2H),3.33(t,2H),2.71(s ,3H),2.33(d,3H),1.38(s,9H),1.18(s,9H),1.80-0.79(m,10H),0.79(d,3H).

[0350] Synthesis example 4

[0351]

[0352] (1) Preparation of ligand compound: Synthesis of N-tert-butyl-1-(1,2-dimethyl-3H-benzo[b]cyclopenta[d]thiophene-3-yl)-1,1-dimethylsilylamine

[0353] 4.65 g (15.88 mmol) of the compound of Chemical Formula 3 was added to a 100 mL Schlenk flask, and then 80 mL of THF was added. After tBuNH2 (4 equivalents, 6.68 mL) was added at room temperature, the mixture was reacted at room temperature for 3 days. After the reaction was completed, THF was removed and the mixture was filtered with n-hexane. After drying the solvent, 4.50 g (yield: 86%) of a yellow liquid was obtained.

[0354] 1 H-NMR (500MHz, CDCl3): δ7.99(d,1H),7.83(d,1H),7.35(dd,1H),7.24(dd,1H), 3.49(s,1H),2.37(s,3H),2.17(s,3H),1.27(s,9H),0.19(s,3H),-0.17(s,3H).

[0355] (2) Preparation of transition metal compounds

[0356] The ligand compound (1.06g, 3.22mmol / 1.0 equivalent) and 16.0mL (0.2M) MTBE were added to a 50mL volumetric flask and stirred first. At -40°C, n-BuLi (2.64mL, 6.60mmol / 2.05 equivalent, 2.5M in THF) was added and reacted overnight at room temperature. Subsequently, MeMgBr (2.68mL, 8.05mmol / 2.5 equivalent, 3.0M in diethyl ether) was slowly added dropwise at -40°C, and TiCl4 (2.68mL, 3.22mmol / 1.0 equivalent, 1.0M in toluene) was then added at room temperature and reacted overnight. The reaction mixture was then filtered through diatomaceous earth using hexane. After drying the solvent, 1.07g (yield: 82%) of a brown solid was obtained.

[0357] 1 H-NMR (500MHz, CDCl3): δ7.99(d,1H),7.68(d,1H),7.40(dd,1H),7.30(dd,1H),3.22(s,1H), 2.67(s,3H),2.05(s,3H),1.54(s,9H),0.58(s,3H),0.57(s,3H),0.40(s,3H),-0.45(s,3H).

[0358] <Preparation of supported catalyst>

[0359] Preparation Example 1: Preparation of hybrid supported metallocene catalyst 1

[0360] 5.0 kg of toluene solution was added to a 20L sus high pressure reactor, and the reactor temperature was maintained at 40° C. 1000 g of silica (manufactured by Grace Davison, SYLOPOL948) vacuum dehydrated at 600° C. for 12 hours was added to the reactor and fully dispersed, and then 80 g of the metallocene compound of Synthesis Example 1 was dissolved in toluene and added thereto, followed by stirring at 200 rpm for 2 hours at 40° C. for reaction. Thereafter, stirring was stopped, sedimentation was allowed to proceed for 30 minutes, and the reaction solution was decanted.

[0361] Add 2.5 kg of toluene to the reactor, add 9.4 kg of 10 wt% methylaluminoxane (MAO) / toluene solution, and then stir at 40°C at 200 rpm for 12 hours. After the reaction, stop stirring, let it settle for 30 minutes, and decant the reaction solution. Add 3.0 kg of toluene, stir for 10 minutes, stop stirring, let it settle for 30 minutes, and decant the toluene solution.

[0362] 3.0 kg of toluene was added to the reactor, and then 314 mL of 29.2 wt % metallocene compound / toluene solution of Synthesis Example 2 was added to the reactor, and then stirred at 40° C. and 200 rpm for 2 hours to react. At this time, the molar ratio of the first metallocene compound to the second metallocene compound was 1:5. After the reactor temperature was lowered to room temperature, stirring was stopped, and the reaction solution was allowed to settle for 30 minutes, and the reaction solution was decanted.

[0363] 2.0 kg of toluene was added, and the mixture was stirred for 10 minutes, then the stirring was stopped, and the mixture was allowed to settle for 30 minutes, and the reaction solution was decanted.

[0364] 3.0 kg of hexane was added to the reactor, and the hexane slurry was transferred to a filter dryer, and the hexane solution was filtered and dried under reduced pressure at 40° C. for 4 hours to prepare 910 g of SiO2 hybrid supported catalyst 1.

[0365] Preparation Example 2: Preparation of Hybrid Supported Metallocene Catalyst 2

[0366] 3.0 kg of the toluene solution was added to a 20Lsus high-pressure reactor, and the reactor temperature was maintained at 40° C. 500 g of silica (manufactured by Grace Davison, SP2212) vacuum-dehydrated at a temperature of 600° C. for 12 hours was added to the reactor and fully dispersed, and then 2.78 kg of a 10 wt% methylaluminoxane (MAO) / toluene solution was added thereto, followed by stirring at 80° C. at 200 rpm for 15 hours to carry out a reaction.

[0367] The reactor temperature was lowered to 40°C, and then 200 g of the first metallocene compound / toluene solution (7.8 wt % in toluene) prepared in Synthesis Example 1 was added to the reactor and stirred at 200 rpm for 1 hour. Subsequently, 250 g of the second metallocene compound (b) / toluene solution (7.8 wt % in toluene) prepared in Synthesis Example 3 was added to the reactor and stirred at 200 rpm for 1 hour (molar ratio of the first metallocene compound: the second metallocene compound = 1:1.3).

[0368] 70 g of the cocatalyst (anilinium tetrakis(pentafluorophenyl)borate) was diluted in toluene and then added to the reactor, followed by stirring at 200 rpm for more than 15 hours. After the reactor temperature was lowered to room temperature, stirring was stopped, and the reaction solution was allowed to settle for 30 minutes and decanted.

[0369] The toluene slurry was transferred to a filter dryer and filtered. After adding 3.0 kg of toluene and stirring for 10 minutes, stirring was stopped and filtered. 3.0 kg of n-hexane was added to the reactor and stirred for 10 minutes, then stirring was stopped and filtered. Drying under reduced pressure at 50° C. for 4 hours prepared 500 g-SiO2 supported catalyst.

[0370] <Preparation of ethylene-α-olefin copolymer>

[0371] Preparation Example 3: Preparation of ethylene / 1-hexene copolymer (PE-a)

[0372] In the presence of the supported hybrid catalyst 1 prepared in Preparation Example 1, an ethylene / 1-hexene copolymer (PE-a) was subjected to slurry polymerization.

[0373] At this time, the polymerization reactor adopts a continuous polymerization reactor of isobutane (i-C4) slurry loop process, the reactor volume is 140L, and the flow rate is about 7m / s. The gases (ethylene, hydrogen) and comonomer 1-hexene required for polymerization are continuously and continuously added, and the flow rate is adjusted according to the target product. At this time, the ethylene input is 31.1kg / hr, the 1-hexene input is adjusted to 2.5% by weight relative to ethylene, and the hydrogen input is adjusted to 56ppm relative to ethylene. In addition, the concentrations of all gases and 1-hexene monomers in Preparation Example 1 are confirmed by an online gas chromatograph. A loaded catalyst is prepared and added in the form of an isobutane slurry with a concentration of 4% by weight, the reactor pressure is maintained at about 40 bar, and the polymerization temperature is about 80°C.

[0374] Preparation Example 4: Preparation of ethylene / 1-hexene copolymer (PE-b)

[0375] Ethylene / 1-hexene copolymers are prepared by a unimodal polymerization process.

[0376] Specifically, the hybrid supported metallocene catalyst 2 prepared in Preparation Example 2 was used, and an ethylene input of 10.0 kg / hr, a 1-hexene input of 6.3 mL / min, and a hydrogen input of 1.73 g / hr were used in a ring reactor having a hexane slurry stirred tank reactor (polymerization temperature: 93° C., polymerization pressure: 7.7 kgf / cm 2 ) to obtain an ethylene / 1-hexene copolymer (PE-b).

[0377] The catalytic activity was determined to be 9.9 kg PE / gCat.hr by measuring the weight of the catalyst used in the polymerization and the weight of the polymer produced in the polymerization and then calculating the weight ratio of the weight of the polymer produced to the weight of the catalyst used.

[0378] Preparation Example 5: Preparation of ethylene / 1-hexene copolymer (PE-c)

[0379] A 1.5L continuous process reactor was preheated at 120°C, while adding 5kg of n-hexane solvent and 0.31kg of 1-octene per hour. Triisobutylaluminum (Tibal, 0.045mmol / min), the transition metal compound obtained in Synthesis Example 4 and dimethylanilinium tetrakis(pentafluorophenyl)borate cocatalyst (2.6μmol / min) were added to the reactor. Subsequently, ethylene (0.87kg / h) and hydrogen (10cc / min) were introduced into the reactor, and a temperature of 160.0°C was maintained at a pressure of 89 bar for more than 60 minutes in a continuous process to carry out copolymerization, thereby obtaining an ethylene / 1-octene copolymer (PE-d).

[0380] Preparation Example 6: Preparation of ethylene / 1-hexene copolymer (PE-d)

[0381] As the ethylene / 1-butene copolymer (PE-d), a commercially available product (LG Chem ME1000, Ziegler-Natta catalyst) was used.

[0382] Preparation Example 7: Preparation of ethylene / 1-hexene copolymer (PE-e)

[0383] As the ethylene / 1-hexene copolymer (PE-e), a commercially available product (LG Chem HP1018, metallocene catalyst) was used.

[0384] Test Example 1: Evaluation of Physical Properties of Polyethylene

[0385] The physical properties of the ethylene-α-olefin copolymers prepared in Preparation Examples 3 to 5 were measured by the following methods, and the results are shown in Table 1.

[0386] (1) Density

[0387] Density (g / cm2) was measured using a density gradient column according to ASTM D 1505 (American Society for Testing and Materials). 3 ).

[0388] (2) Melt index

[0389] Melt Index (MI 2.16 ) is measured at 190° C. and a load of 2.16 kg (measuring apparatus: MI-4, manufactured by Gottfert) in accordance with ASTM D 1238 (Condition E, 190° C., 2.16 kg) of the American Society for Testing and Materials, and is expressed as the weight (g) of the polymer melted for 10 minutes.

[0390] (3) Number average molecular weight (Mn), weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn)

[0391] Regarding the ethylene-α-olefin copolymers prepared in Preparation Examples 1 to 4, the weight average molecular weight (Mw, g / mol) and the number average molecular weight (Mn, g / mol) were measured using gel permeation chromatography (GPC, manufactured by Waters Corporation) according to ASTM D 6474 (American Society for Testing and Materials), and then the molecular weight distribution (Mw / Mn, PDI, polydispersity index) was calculated by dividing the weight average molecular weight by the number average molecular weight.

[0392] Specifically, a PL-GPC220 manufactured by Waters was used as a gel permeation chromatography (GPC) instrument, and a Polymer Laboratories PLgelMIX-B 300 mm long chromatographic column was used. The evaluation temperature was 160 ° C, the solvent was 1,2,4-trichlorobenzene, and the flow rate was 1 mL / min. The various ethylene-α-olefin copolymer samples prepared in Preparation Examples 1 to 2 were dissolved in 1,2,4-trichlorobenzene containing 0.0125% BHT at 160 ° C for 3 hours for pretreatment by using a GPC analyzer (PL-GP220), and a sample with a concentration of 32 mg / 10 mL was injected in an amount of 200 μL. The calibration curve formed using polystyrene standards was used to obtain Mw and Mn. Nine polystyrene standards were used with molecular weights of 2000 g / mol, 10000 g / mol, 30000 g / mol, 70000 g / mol, 200000 g / mol, 700000 g / mol, 2000000 g / mol, 4000000 g / mol and 10000000 g / mol.

[0393] [Table 1]

[0394]

[0395] <Preparation of Polyethylene Composition>

[0396] Examples 1 to 3 and Comparative Examples 1 to 3

[0397] The polyethylene compositions of Examples 1 to 3 and Comparative Examples 1 to 3 were prepared using the ethylene-α-olefin copolymers of Preparation Examples 3 to 7, respectively, and their compositions are shown in Table 2 below.

[0398] Specifically, a polyethylene composition was prepared by extrusion pelletization at 220° C. with a hopper at 18 rpm and a screw at 350 rpm using a twin extruder (extruder: TEK30MHS of SMPLATEK, L / D: 40, die diameter: 4 mm).

[0399] Test Example 2: Evaluation of Physical Properties of Polyethylene

[0400] The physical properties of the polyethylene compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were measured by the following methods. The results are shown in Table 2.

[0401] First, the melt index (MI) of the polyethylene composition was measured using the same method as in Test Example 1. 2.16 ), density, weight average molecular weight (Mw, g / mol), number average molecular weight (Mn, g / mol) and molecular weight distribution (Mw / Mn, PDI).

[0402] (1) Melting temperature (Tm), crystallization temperature (Tc) and crystallinity (%)

[0403] The melting temperature (Tm), crystallization temperature (Tc), and crystallinity (Xc) of the polyethylene compositions of Examples 1 to 3 and Comparative Examples 1 to 3 were measured using a differential scanning calorimeter (DSC, equipment name: DSC Q20, manufacturer: TA Instruments).

[0404] Specifically, the polyethylene composition is heated to 180°C at a rate of 10°C / min (cycle 1), isothermally maintained at 180°C for 5 minutes, cooled to 0°C at a rate of 10°C / min, isothermally maintained at 30°C for 5 minutes, and then heated to 180°C again at a rate of 10°C / min (cycle 2). In the above DSC curve, the temperature at the highest point of the endothermic peak is measured as the melting temperature (Tm, °C), and the temperature at the highest point of the exothermic peak is measured as the crystallization temperature (Tc, °C). At this time, the melting temperature (Tm) and the crystallization temperature (Tc) are as shown in the results of measurement in the cycle 2 of the second temperature rise and fall.

[0405] Furthermore, the heat of fusion ΔHm was obtained by calculating the area of ​​the melting peak of the second temperature rise in cycle 2, and the crystallinity (Xc, %) was calculated by dividing ΔHm by the theoretical value H0m=293.6 J / g when the crystallinity was 100%.

[0406] (2) Fraction of ligament molecules (weight %)

[0407] According to the method described in US Pat. No. 10,775,287, the tie molecule fractions of the polyethylene compositions of Examples and Comparative Examples were calculated from Equations 1 to 4 described above.

[0408] (3) Natural tensile ratio (NDR, %), elongation at break at 120℃ (%), yield strength at 120℃ (MPa), 1% modulus at 120℃ (MPa)

[0409] First, each composition in Examples and Comparative Examples was press-molded at a temperature of 180° C. and a pressure of 4500 lbf for 15 minutes to prepare a sheet having a thickness of 1 mm, and then a tensile test specimen was prepared according to ASTM D 638.

[0410] According to ASTM D638, the specimens were subjected to a tensile test at room temperature (25°C) at a tensile rate of 500% / min. Figure 1 From these tensile test results, the natural draw ratio (NDR) was calculated as the elongation before the strain hardening point on the tensile curve.

[0411] In addition, according to ASTM D638, a high temperature tensile test was conducted on the tensile specimens using a UTM device (universal tensile testing machine) equipped with an oven at a tensile rate of 1000% / min and a temperature of 120°C. The results of the high temperature tensile test are shown in Figure 2. Figure 2 According to these tensile test results, the elongation at break at 120°C is calculated as the elongation at break of the sample.

[0412] In addition, according to Figure 2 The 120°C yield strength (defined as the tensile strength at the transition point from the elastic region to the plastic region) was calculated from the tensile curve obtained from the medium and high temperature tensile test results, and the 1% modulus was obtained by calculating the tensile modulus from the starting point of the tensile curve to the elongation of 1%.

[0413] [Table 2]

[0414]

[0415]

[0416] Test Example 3: Preparation and physical property evaluation of biaxially stretched film

[0417] Biaxially stretched films were prepared using the polyethylene compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 3 in the following manner, and their physical properties were measured. The results are shown in Table 3.

[0418] Preparation of biaxially stretched films

[0419] - 0.75 mm polyethylene composition sheet using a laboratory extruder line manufactured by Bruckner (L / D ratio: 42, screw diameter: 25 mm, melt / T die temperature: 220°C)

[0420] - Biaxial stretching of polyethylene composite sheets with a length and width of 90 mm x 90 mm using KARO 5.0 equipment

[0421] -After preheating for 80 seconds under the following conditions, continuous stretching (MD→TD) was performed (Example 1: preheating and stretching at 120°C; Example 2: preheating and stretching at 125°C; Example 3: preheating and stretching at 122°C; Comparative Example 1: preheating and stretching at 115°C; Comparative Example 2: preheating and stretching at 125°C; Comparative Example 3: stretching was attempted under the same conditions as in Comparative Example 2, but it was determined that stretching was not possible).

[0422] Evaluating the physical properties of biaxially stretched films

[0423] -Haze (%): Measured according to ASTM 1003

[0424] - Gloss (45°): measured according to ASTM 2457

[0425] -Tensile strength (MPa), biaxial tensile modulus (MPa) and tensile elongation (%): measured in MD / TD according to ASTM D 882

[0426] -Tear strength (N / mm): measured in MD / TD direction according to ASTM 1922

[0427] - Shrinkage (%): The length change was measured after shrinking at 100° C. or 120° C. for 7 minutes according to ASTM D 1204. Specifically, the shrinkage (%) was measured as [(1-length after shrinkage) / length before shrinkage]*100.

[0428] -Puncture strength (N / mm): measured according to ASTM 14477

[0429] [Table 3]

[0430]

[0431] According to the results of Table 2 and Table 3, compared with the comparative example, the composition of the example satisfying the predetermined tie molecule fraction and NDR has excellent stretchability and stretching stability when made into a biaxially stretched film, and exhibits excellent mechanical properties.< / r> < / r>

Claims

1. A polyethylene composition comprising at least one ethylene-α-olefin copolymer, in, The tethered molecule fraction obtained from the crystallinity and crystal structure analysis results is 4.5 wt % to 7.0 wt %, and The natural draw ratio (NDR) measured by a tensile test at a tensile speed of 500% / min on a sheet specimen having a thickness of 1 mm according to ASTM D638 is 600% or more.

2. The polyethylene composition according to claim 1, wherein The polyethylene composition comprises: (a) a first ethylene-α-olefin copolymer having a density of 0.930 g / cm 3 Up to 0.960g / cm 3 And melt index (MI 2.16 , 190°C, 2.16 kg load) is 0.2 g / 10 min to 2.0 g / 10 min; and (b) a second ethylene-α-olefin copolymer having a density of 0.870 g / cm 3 Up to 0.920g / cm 3 And melt index (MI 2.16 , 190°C, 2.16kg load) is 3.0g / 10min to 10.0g / 10min.

3. The polyethylene composition according to claim 2, wherein The content of the first ethylene-α-olefin copolymer (a) is 60 wt% or more and 90 wt% or less, and The content of the second ethylene-α-olefin copolymer (b) is 10% by weight or more and 40% by weight or less.

4. The polyethylene composition according to claim 1, wherein Density measured according to ASTM D 1505 is 0.925 g / cm 3 Above 0.939g / cm 3 The following, and MI (190° C., 2.16 kg) measured in accordance with ASTM D 1238 is 0.3 g / 10 min or more and 1.5 g / 10 min or less.

5. The polyethylene composition according to claim 1, wherein The number average molecular weight (Mn) is above 15000 g / mol, The weight average molecular weight (Mw) is 100000 g / mol or more, and Mw / Mn is 10.0 or less.

6. The polyethylene composition according to claim 1, wherein The melting point (Tm) is 127°C or higher and 130°C or lower. The crystallization temperature (Tc) is 112°C or higher and 115°C or lower, and The crystallinity (Xc) is 37% or more and 50% or less.

7. The polyethylene composition according to claim 2, wherein The first ethylene-α-olefin copolymer (a) has: A number average molecular weight (Mn) of 12000 g / mol or more and 50000 g / mol or less, a weight average molecular weight (Mw) of 100,000 g / mol or more and 250,000 g / mol or less, and Molecular weight distribution (Mw / Mn) of 3.0 or more and 20.0 or less.

8. The polyethylene composition according to claim 2, wherein The first ethylene-α-olefin copolymer (a) is an ethylene / 1-hexene copolymer.

9. The polyethylene composition according to claim 2, wherein The second ethylene-α-olefin copolymer (b) has: A number average molecular weight (Mn) of 20,000 g / mol or more and 50,000 g / mol or less, a weight average molecular weight (Mw) of 50,000 g / mol or more and 100,000 g / mol or less, and Molecular weight distribution (Mw / Mn) of 2.0 or more and 4.0 or less.

10. The polyethylene composition according to claim 2, wherein: The second ethylene-α-olefin copolymer (b) is an ethylene / 1-octene copolymer.

11. The polyethylene composition according to claim 1, wherein The elongation at break measured by a tensile test conducted at 120° C. and a tensile speed of 1000% / min on a sheet specimen having a thickness of 1 mm according to ASTM D638 is 3000% or more.

12. The polyethylene composition according to claim 11, wherein Calculated from the tensile test results, the yield strength at 120° C. is 4.0 MPa or more, and the 1% modulus is 4.0 MPa or more. 13 . A biaxially stretched film comprising the polyethylene composition according to claim 1 .

14. The biaxially stretched film according to claim 13, wherein The biaxially stretched film is stretched at an MD stretch ratio of more than 4 times and a TD stretch ratio of more than 6 times.

15. The biaxially stretched film according to claim 13, wherein The haze is less than 2.0%, and the glossiness at 45° is 80 GU or more.

16. The biaxially stretched film according to claim 13, wherein The average value of MD tensile strength and TD tensile strength measured according to ASTM D 882 is 130 MPa or more.